Effect of ultra-processed–rich versus ultra-processed–free preload meals at high and low energy density on ad libitum energy intake: a randomized crossover trial - Ludmila de Melo Barros; Micnéias Roberth Pereira; Vanessa Amorim Peixoto; Guilherme César Oliveira de Carvalho; Débora Cavalcante Ferro; Marianna Victória Cerqueira Rocha; Déborah Tenório da Costa Paula; Délis Barbosa Soares; Isabelle Rodrigues de Souza Gama; Priscila Adelina Alves Viana; Rodrigo Tenório Lins Carnaúba; Thayná Xavier Rocha de Oliveira; et al. (Appetite, 2027)

Genomic analysis of Escherichia coli, Enterobacter hormaechei, and Cupriavidus gilardii isolated from Cacatua alba - Julia Penna de Andrade; Henrique da Silva Vieira; Camilla Faria Soares; Marcela Laryssa Oliveira Duarte; André Almeida Fernandes; Hannah Luiza Gonsalves Coelho; Victória Veiga Alves; Bertram Brenig; Vasco Ariston de Carvalho Azevedo; Flávia Figueira Aburjaile; Nelson Rodrigo da Silva Martins (Veterinary Research Communications, 2026)
The objective of this study was to perform genomic, phylogenomic, and phenotypic characterization of bacterial isolates from a captive Cacatua alba to investigate their antimicrobial resistance profiles, virulence-associated genes, and genomic relationships with publicly available strains. Bacterial isolates obtained from the lungs and encephalon were identified as Escherichia coli (AV037), Enterobacter hormaechei (AV038), and Cupriavidus gilardii (AV039). Comparative genomic analyses, phylogenomic reconstruction, and antimicrobial susceptibility testing (AST) were performed. Genomic analysis identified multiple antimicrobial resistance-associated genes in AV037, AV038, and AV039, with genes associated with efflux pumps, particularly those in the resistance-nodulation-cell division (RND) family, as the predominant resistance-associated mechanism identified. Most identified genes are intrinsic to the respective bacterial species and do not necessarily confer phenotypic antimicrobial resistance when present alone. Phenotypic testing confirmed multidrug-resistant (MDR) profiles, with resistance to β-lactams and aminoglycosides. Susceptibility to carbapenems was preserved in AV037 and AV038, whereas AV039 exhibited resistance to meropenem. Phylogenomic analysis demonstrated that AV037 and AV038 clustered with strains recovered from diverse hosts and geographic regions. In contrast, AV039 clustered predominantly with environmental and human-associated isolates, including strains harboring the mcr-5 gene. These findings are consistent with previous reports describing the recovery of C. gilardii from both environmental and clinical sources. Overall, this study documents the occurrence of MDR bacteria carrying resistance and virulence-associated determinants in a captive C. alba , highlighting the value of genomic surveillance to improve our understanding of the distribution of clinically relevant bacterial isolates across different ecological settings.

Contaminants of emerging concern in seafood: a scoping review of exposure-based risk evidence and critical considerations for future regulation - Milena Dutra Pierezan; Luan Valdemiro Alves de Oliveira; Rodrigo Barcellos Hoff; Silvani Verruck (Food Control, 2026)

In Silico discovery and preliminary serological evaluation of an NcSRS2-derived synthetic peptide for the diagnosis of Neospora caninum in dogs and cattle - Maria Lorenza Leal Motta; Diogo Fonseca Soares Pereira; Juliana Rodrigues Moraes; Rodrigo Moreira Verly; Luís Fernando Pita Gondim; Clelton Aparecido dos Santos; Alexsandro Sobreira Galdino; Walderez Ornelas Dutra; Olindo Assis Martins-Filho; Lis Ribeiro do Valle Antonelli; Renato Andreotti; Ronaldo Alves Pinto Nagem; et al. (Veterinary Parasitology, 2026)

Developmental effects of intrauterine and lactational exposure to nanoplastics and phthalates on rat testis - Mirella Franco Moreira; Natália Magosso; Patrick Vieira de Souza; Matheus Naia Fioretto; Isabela Silva Ferreira; Vanessa Aguiar Rocha; Victória Cristina Pinha; Débora Hipólito Quadreli; Glaura Scantamburlo Alves Fernandes; Luis Antonio Justulin; Jodi Anne Flaws; Wellerson Rodrigo Scarano (Environmental Pollution, 2026)

Collaborative monitoring networks refine jaguar habitat suitability and reveal conservation gaps in the Brazilian Cerrado - Lucas Gonçalves da Silva; Marco Aurélio Mendes Elias; Juliana Silveira dos Santos; Anah Tereza de Almeida Jácomo; Douglas Santos; Ennio Painkow Neto; Fabio Hudson Souza Soares; Gabriel Caputo de Carvalho; Giselle Bastos Alves; Gonzalo Barquero; Igor Fagundes Perfeito; Marina Motta de Carvalho; et al. (Biological Conservation, 2026)

Association of the endosomal TLR4 pathway with dorsolateral prostatic remodeling induced by perinatal phthalate mixture exposure in rats - Vinícius Luís Rocha da Silva Maria; Ana Clara Pacheco de Santana; Patrick Vieira Souza; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Natália Magosso; Mirella Franco Moreira; Maria Clara Betete Da Silva Fonseca; André Mascarenhas Guariento; Sergio Pereira; Ariana Musa Aquino; Letícia P. Bomfim; et al. (Reproductive Toxicology, 2026)

A One Health approach to investigate potential association between producing aspects and antibiotic resistance in the dairy production chain, based on Escherichia coli as sentinel - Milimani Andretta; Rafaela de Melo Tavares; Bruna Torres Furtado Martins; Rodrigo Alves Barros; Luciano dos Santos Bersot; Ricardo Seiti Yamatogi; Brooke Monroe Ramay; Luís Augusto Nero (International Dairy Journal, 2026)

Large-scale toxic bloom of Dinophysis acuminata complex following a major flood disaster in southern Brazil - Luiz L. Mafra; Bruna Fernanda Sobrinho; Ana Martínez; Karoline Magalhães F. Lubiana; Regiane Valejo Maciel; José Guilherme F. Bersano; Luciano F. Fernandes; Fabiola Kaviatkovski; Pedro Almeida Rodrigo; Rafaela Cristine Zem; Carlos E.J.de Azevedo Tibiriçá; Mathias Alberto Schramm; et al. (Harmful Algae, 2026)

Employing a Hiblack carbon-based gas diffusion electrode for in situ H2O2 generation while valorizing urine organic matter - Raul José Alves Felisardo; Oswaldo Costa Junior; Raira Souza de Santana Castro; Rafael Granados-Fernández; Marcos R.V. Lanza; Manuel A. Rodrigo (Chemical Engineering Journal, 2026)

Effect of the genetic merit for backfat thickness on the meat quality of steers - Thiago Luís Alves Campos de Araújo; Gelson Luís Dias Feijó; Marina de Nadai Bonin Gomes; Elzania Sales Pereira; Gilberto Romeiro de Oliveira Menezes; Ériklis Nogueira; Luiz Orcírio Fialho de Oliveira; Andrei Pereira Neves; Jaqueline Rodrigues Ferreira; Karla Izidio Latta; Douglas Gomes Vieira; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2026)
The objective of the present study was to evaluate the effects of the genetic merit for backfat thickness (GMB) and subcutaneous fat thickness (FT) on meat quality traits of Nellore and crossbred (½ Aberdeen Angus + ½ Nellore) steers. The animals were obtained by mating Nellore cows with Nellore or Aberdeen Angus bulls. Both paternal genetic groups were selected to provide positive (+, high GMB) or negative (-, low GMB) expected progeny differences (EPDs) in terms of backfat thickness. Two hundred and fourteen animals were obtained, reared on a pasture, and finished either in feedlot or semi-confinement systems. The steers were slaughtered, and the backfat visual scores, FT, marbling visual scores and meat color aspects were evaluated for the carcasses (24 h postmortem). In non-aged and aged meat samples (for 14 days), the pH, color, drip loss, cooking loss, and shear force were analyzed. The moisture content and intramuscular fat concentrations of the meat were determined. A second experimental approach was proposed to assess the influence of the FT class (low = 3.66 ± 0.58 mm; medium = 4.99 ± 0.49 mm and high = 6.81 ± 1.06 mm) on the same variables as in the original study. The GMB influenced ( P < 0.05) the FT and carcass fattening but did not influence ( P > 0.05) the physicochemical traits or the fat content of the meat. Steers with a low, medium, or high FT provided meats with similar physicochemical attributes. Thus, GMB increases subcutaneous fat deposition without affecting meat quality traits.

Alterations of cryptogam communities over one decade of time on King George Island, Antarctica - Rodrigo Paidano Alves; Bettina Weber; Cybelli G. G. Barbosa; Adam Thomas Clark; Filipe de Carvalho Victoria; Margéli Pereira de Albuquerque; Antonio Batista Pereira (Polar Biology, 2026)
Antarctica’s ice-free areas are mainly colonized by cryptogamic communities, which are known to be sensitive indicators of environmental change. Despite numerous monitoring-related studies, published research on medium-term cryptogam cover changes is limited. With this study, we aimed to investigate compositional and structural changes in cryptogamic communities over a decade near the Polish Arctowski Antarctic Station. Here, a phytosociological approach was used to assess species diversity, coverage, and ecological relevance during the 2012–2013 field campaign, with results being compared to a previously published survey conducted in 2003–2004. Climatic trends were assessed to identify potential environmental drivers for the observed vegetation changes. Results revealed lower moss richness and lower ecological relevance based on coverage and frequency, particularly among cushion-forming taxa such as Andreaea gainii and Syntrichia princeps . In contrast, lichen richness increased, with species such as Usnea aurantiacoatra increasing in ecological importance, while U. antarctica declined. These species-specific trends suggest that traits such as moisture tolerance, growth form, and substrate preference influence the capacity of cryptogams to respond to changing conditions. Climatic data indicate no significant changes in temperature, relative humidity, or precipitation (2003–2013), while the long-term record showed weak trends (1990–2020). Therefore, medium-term climatic data did not support a direct attribution of the observed vegetation changes to climate variables. These findings demonstrate that successional processes and local site conditions can be associated with measurable ecological restructuring in Antarctic vegetation. By providing high-resolution floristic and ecological data, this study establishes a baseline for future monitoring, using cryptogams as indicators of environmental change.

Climate change and conservation of threatened tree species in the Doce River Basin: an ecological niche modeling approach - Cecília Loren-Silva; Rodrigo Gomes Gorsani; Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Rafaela Brandão-Gomes; Renato Augusto Ferreira de Lima; Carlos Moreira Miquelino Eleto Torres; Nathália Silva; Marcelo Simonelli; Markus Gastauer; Fabiana Bonani; João Augusto Alves Meira-Neto (Biodiversity and Conservation, 2026)
Tropical forests, particularly the Atlantic Forest, are among the most biodiverse and threatened ecosystems on Earth. Intense fragmentation, historical deforestation, and climate change have compromised their integrity and endangered endemic and rare species. The situation is even more critical in the Doce River Basin (DRB), a biodiversity hotspot in southeastern Brazil, due to the expansion of pastureland and mining, as well as the 2015 Mariana disaster. Understanding how future climate may affect the persistence of threatened tree species in the region is essential. This study evaluated the effects of climate scenarios on the distribution of 26 rare and/or threatened tree species in the DRB. We used Species Distribution Models (SDMs), combining algorithms (GLM, RDF, SVM, MaxEnt) into a consensus ensemble model under SSP3-7.0 and SSP5-8.5 scenarios for 2050 and 2090. Climatic, topographic, and edaphic variables were predictors, with climate explaining most environmental variation. Among the 26 species, 19 are projected to lose over 75% of their suitable area, with local extinction likely for range-restricted and specialized species such as Handroanthus arianeae and Grazielodendron rio-docensis . Species associated with mature forests and humid microclimates were most severely affected, while some generalists showed resilience, maintaining or expanding suitable areas. Although all species retain some suitable habitats within Protected Areas (PAs), results indicate the current PA network will be insufficient for long-term conservation. Complementary strategies such as assisted translocation, habitat connectivity, and priority-area identification based on climate projections are needed. This study provides critical insights for policies and land-use planning aimed at conserving the DRB’s threatened flora.

Circulating Matrix Metalloproteinase Activity and Functional Capacity in Individuals Undergoing Hemodialysis: Exploratory Findings from a Resistance Training Trial - Hugo de Luca Correa; Rafael Lavarini dos Santos; Ivo Vieira Sousa de Neto; Rodrigo Vanerson Passos Neves; Thaís Amaral Ferreira Baracho; Taynah Oliveira Martins; Jéssica Mycaella da Silva Barbosa; Thaís Branquinho de Araújo; Leandro Lima Sousa; Rebecca Salomão; Rita de Cássia Marqueti; Lysleine Alves de Deus; et al. (Journal of Science in Sport and Exercise, 2026)
Purpose To investigate the effects of 24 weeks of resistance training (RT) on pro- and active matrix metalloproteinases (MMPs) and their association with functional performance in end-stage kidney disease (ESKD) patients undergoing hemodialysis. Methods Forty-two ESKD patients (mean age: 65 ± 4 years; dry body mass: 71 ± 16 kg; body mass index: 25 ± 3 kg/m 2 ) were randomized into two groups: the control (CTL, n = 20) and RT group ( n = 22). RT was comprised three times per week for 24 weeks. Plasma MMP-2 and MMP-9 activity were assessed by zymography. Functional and body-composition outcomes included handgrip strength, fat-free mass (FFM), 5-min walking test, and the Timed Up and Go (TUG) test. Results Using bioinformatics tools, we found that MMP-2 gene expression in PBMCs was decreased in ESKD patients undergoing hemodialysis. At post-intervention, RT displayed a higher active MMP-2 activity, while MMP-9 did not change. After baseline adjustment, the estimated effect of RT on active MMP-2 was attenuated, whereas active MMP-9 showed a lower adjusted response in the RT group. Active MMP-2 activity was positively associated with handgrip strength, FFM ( P P Conclusion RT improved functional outcomes and the complex effects of RT on MMPs should be thoroughly investigated in future experimental and clinical studies.

From nitrogen and calcium supply to field performance: a long-term study on sustainable nutrient management in citrus production - Gabriel Antonio Bortoloti; Rodrigo Marcelli Boaretto; Geraldo José Silva; José Antônio Quaggio; Guilherme Oliveira Silva; Alexandre Alves da Silva; Márcio Augusto Soares; Thais Regina Souza Chiachia; Franz Walter Rieger Hippler; Dirceu Mattos (Plant and Soil, 2026)
Background and aims Sustainable citrus production requires nitrogen (N) management strategies that account for soil–plant nutrient interactions, particularly those affecting calcium (Ca) nutrition. In fertigated citrus orchards, strategies differing in NO₃⁻:NH₄⁺ balance and associated Ca supply affect soil chemical properties, plant nutritional status, fruit yield, and NUE. This study evaluated the effects of contrasting fertigation strategies, with or without foliar Ca application in a sweet-orange orchard. Methods A split-plot field experiment was conducted from 2020–23. Subplots received 220 kg N ha⁻ 1 yr⁻ 1 as calcium nitrate (CN; 100:0 NO₃⁻:NH₄⁺), nitrate-dominant mixture of calcium nitrate and ammonium nitrate (CN + AN; 75:25 NO₃⁻:NH₄⁺), or ammonium nitrate (AN; 50:50 NO₃⁻:NH₄⁺). Main plots received or not foliar Ca. Soil chemical properties, leaf nutrient status, fruit yield, and NUE were evaluated. Results CN and CN + AN were associated with higher soil pH and Ca availability, as well as approximately 15% higher leaf Ca concentration compared to AN. Responses were accompanied by higher fruit yield and NUE, with CN and CN + AN producing about 10 t ha⁻ 1 more fruit than AN across four harvests. Fruit yield was positively correlated with both leaf Ca concentration and leaf Ca:N ratio. Foliar Ca application did not improve leaf Ca concentration or fruit yield, and its association with lower NUE reflected the additional N supplied via Ca(NO₃)₂ without a corresponding increase in yield. Conclusion Fertigation differing in NO₃⁻:NH₄⁺ balance and Ca supply influenced soil chemical properties, plant nutritional status, fruit yield, and NUE. CN + AN was the best fertigation practice, whereas foliar Ca application provided no additional benefit to trees.

Integrative molecular epidemiology of Sporothrix in Latin America reveals calmodulin genotypes associated with host, clinical form and geographic distribution - Pedro Henrique Oliveira Favacho; Hellaine Cristina Gonçalves Mota; Gabriel Silas Marinho de Sousa; João Gabriel Souza Alves da Silva; Alice Campos Ferreira; Allan Natividade Odorizzi; Emily Vitória Gama de Oliveira; Ruy Marques Bezerra Neto; Nadya Rafaelly dos Passos Pereira; Ester Sousa Costa; Daniel dos Santos Caldas; Silvia Helena Marques da Silva; et al. (Biologia, 2026)
Sporothrix species are the etiological agents of sporotrichosis, an emerging fungal disease of medical and veterinary importance. Molecular surveillance using publicly available databases enables the monitoring of pathogen dissemination and the identification of genetic and epidemiological patterns, particularly in endemic regions. This study aimed to perform an integrative analysis of clinical, epidemiological and phylogenetic characteristics of Sporothrix strains in Latin America based on calmodulin ( CAL ) gene sequences deposited in GenBank between 2014 and 2023. Sequences were selected according to predefined inclusion criteria, including species identification, year of deposition and availability of clinical and epidemiological metadata. Phylogenetic reconstruction was performed using MAFFT and IQ-TREE under the K2P + G4 model with 1,000 bootstrap replicates. Principal Component Analysis and Permutational Multivariate Analysis of Variance (PERMANOVA) were applied to evaluate genetic and epidemiological clustering. A total of 571 sequences were included. Sporothrix brasiliensis was the most frequent species (53.41%), predominantly associated with humans (68.52%) and felines (24.64%), followed by S. schenckii (40.28%). Phylogenetic analysis identified three clades for S. brasiliensis (b1–b3) and S. schenckii (s1–s3), whereas S. globosa formed a single, homogeneous clade (g1). Multivariate analysis resolved three clusters for each species, with S. brasiliensis showing a highly structured grouping driven strictly by the host factor (PERMANOVA Pseudo-F = 23.08, p = 0.001), while S. schenckii exhibited pronounced geographic and clinical variance partitioning (p = 0.001). The integrative interpretation of phylogenetic, multivariate, and epidemiological data indicated geographically restricted genotypes for S. brasiliensis and transnational genotypes for S. schenckii and S. globosa , as well as species-specific host and clinical associations.These findings demonstrate that CAL -based integrative analyses of publicly available data can reveal regional genetic structure and dispersion patterns of Sporothrix species, highlighting the zoonotic relevance of S. brasiliensis and supporting the need for standardized molecular surveillance strategies in Latin America.

Comparative in vitro response of canine, human, and murine osteosarcoma cell lines to resveratrol, homeopathic mistletoe (V.A. CH200), and doxorubicin - Felipe César da Silva Brasileiro; Giovana Pedro; Mayara Simão Franzoni; Rodrigo Cardoso de Oliveira; Cristina Oliveira Massoco Salles Gomes; Flávia Karina Delella; Carlos Eduardo Fonseca-Alves; Renée Laufer-Amorim (Research in Veterinary Science, 2026)

Advancing wastewater sustainability through electro-refineries: Oxalic acid valorization - Rainy Alves de Sousa; Suelya da S. Mendonça de Paiva; Raúl García-Cervillla; Jussara C. Cardozo; Carlos A. Martínez-Huitle; Elisama V. dos Santos; Justo Lobato; Manuel A. Rodrigo (Journal of Environmental Chemical Engineering, 2026)

Long‑term impacts of a composted sewage sludge–based Class B organic fertilizer on soil micronutrients and crop production in the Tropics - Luana Corrêa Silva; Aline Renée Coscione; Rodrigo Silva Alves; Philippe Solano Toledo Silva; Adrielle Rodrigues Prates; Leiliane Dutra Silva; Fabrício da Silva Vasconcelos; Jussara Borges Regitano; Cassio Hamilton Abreu-Junior; Wanderley José de Melo; Gian Franco Capra; Arun Dilipkumar Jani; et al. (European Journal of Agronomy, 2026)

Toward process-based causality indicators for assessing and monitoring ecological impacts of offshore wind energy: a benthic perspective - Ivan Rodrigo Abrão Laurino; Anna Thereza dos Santos Alves Silva; Bruno Olian; Márcia Regina Denadai; Luis Enrique Sánchez; Alexander Turra (Environmental Monitoring and Assessment, 2026)
Offshore wind energy (OWE) is rapidly emerging and expanding in several countries worldwide. A current challenge is understanding the ecological-causal processes underlying OWE environmental impacts to determine appropriate indicators for baseline assessment and follow-up monitoring. Here, we reviewed the ecological impacts and screened parameters that can serve as process-based indicators of causality for assessing and monitoring changes in benthic environments associated with OWE development. To this end, we first conducted a global literature review (73 articles) to compile evidence on OWE impacts on benthic environments. Next, based on the assessed evidence, we designed conceptual-qualitative ecosystem models to clarify the ecological-causal processes connecting OWE pressures with their potential cascading effects. Lastly, we identified ecological parameters from the reviewed literature that could serve as indicators of the processes described by the models. As key results, we detailed the causal chain of OWE effects on benthic environments and proposed 32 indicators for assessing and monitoring impacts. We highlighted that the causal meaning of the indicators, from a process-based perspective, depends on considering biodiversity categorized by life-history traits, rather than relying on general parameters such as the total abundance of the benthic community. This includes classifying species into ecological functional groups that will signal distinct causal processes, such as noise pollution, organic enrichment, and changes in ecosystem functioning. Such a tool can be further applied in baseline and monitoring studies to guide Environmental Impact Assessment toward a process-based praxis that is more aligned with the principles of Ecosystem-Based Management.

Genotoxicity and oral tissue damage associated with tooth bleaching agents: A scoping review - Patrick Wesley Marques de Boa; Mariana Silva de Bessa; Flávio Pereira dos Santos Filho; Lara Beatriz Nascimento Diniz; Rodrigo Othávio de Assunção e Souza; Laércio Almeida de Melo; Arthur Cesar de Medeiros Alves; Boniek Castillo Dutra Borges (Mutation Research - Reviews in Mutation Research, 2026)

Evaluation of the retention process of bile acids by cell surface of inactivated Lacticaseibacillus rhamnosus GG using spray drying under in vitro digestion simulation - Douglas Xavier-Santos; Rodrigo Dias Requião; Paulo César Martins Alves; Christopher Schmidt; Thomas Kurth; Adriane Elisabete Costa Antunes; Stephanie Bader-Mittermaier; Peter Eisner; Anderson S. Sant’Ana (Food Bioscience, 2026)

A comparison of two vitrification methods and the effect of dimethyl sulfoxide in vitrification solution for cryopreservation of Euterpe edulis Martius (Arecaceae) - Débora Pellanda Fagundes; Joana Silva Costa; Ingridh Medeiros Simões; Simone Wellita Simão de Carvalho; Caroline Palacio de Araujo; Lana Laene Lima Dias; Eduardo Alves; Elias Terra Werner; Edilson Romais Schmildt; Amir Ali Khoddamzadeh; Wagner Campos Otoni; Rodrigo Sobreira Alexandre (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Euterpe edulis Martius (Arecaceae) is a native species of the Atlantic Forest hotspot with ecological and economic relevance. Its fruits contribute to biodiversity maintenance by feeding birds and mammals and are valued for their antioxidant properties and applications in the food and cosmetic industries. However, habitat loss and propagation constraints have contributed to the threatened status of this species, reinforcing the need for complementary ex situ conservation strategies. Thus, this study evaluated the cryopreservation of somatic embryos of E. edulis using conventional vitrification and droplet vitrification in association with a modified Plant Vitrification Solution 3 (PVS3) supplemented with different concentrations of dimethyl sulfoxide (DMSO; 0, 5, 10, and 15%). No significant differences were observed between vitrification methods regarding post-thaw recovery. However, PVS3 supplemented with 10% and 15% DMSO promoted higher survival than 0% and 5%, with maximum values recorded at 15% DMSO (67.50% in droplet vitrification and 69.50% in conventional vitrification). Scanning electron microscopy revealed greater structural alterations in somatic embryos at more advanced maturation stages after cryopreservation, whereas transmission electron microscopy showed treatment-dependent differences in cellular ultrastructure, including vacuolization, cell wall disruption, and preservation of nuclear organization in surviving cells. Elemental analysis by energy-dispersive X-ray spectroscopy (EDS) revealed differences among cryopreservation treatments, with higher carbon intensity observed in treatments showing greater post-thaw survival and lower carbon intensity associated with reduced survival. This technique demonstrates potential for preserving germplasm of endangered E. edulis adult plants and can strategically support genetic improvement programs.

Temporal dynamics of thermal warming in brown trout hepatocyte spheroids: ultrastructural and immunocytochemical evidence of cellular remodelling - Rodrigo Alves; Fernanda Malhão; Célia Lopes; Eduardo Rocha; Tânia Vieira Madureira (Cell and Tissue Research, 2026)
Temperature is a key environmental driver of hepatic physiology in ectotherms, and three-dimensional (3D) fish liver models may serve as an ethically advantageous platform to investigate warming effects under controlled conditions while reducing the need for experimental animals. Despite their increasing use in toxicology, their application to assess climate-relevant temperature effects on liver function remains limited. This study investigated the temporal effects of a warming scenario on primary hepatocyte spheroids from juvenile brown trout ( Salmo trutta ), a bioindicator species. The study explores how a + 3 °C increase can affect spheroid development and maintenance, as well as its impact on metabolic activity, cell proliferation and death, and morphology over time. Spheroids were maintained at 18 °C and 21 °C for 25 days and analysed at five time points using metabolic, morphometric, immunocytochemical, and ultrastructural approaches. Mitochondrial metabolic activity, assessed by resazurin reduction, showed no significant temperature-related differences. In contrast, warming accelerated spheroid formation and produced larger spheroids. Proliferative activity, assessed by proliferating cell nuclear antigen (PCNA) immunostaining, was significantly reduced at 21 °C, while caspase-3 levels remained unchanged, indicating no increase in apoptosis. The autophagy marker microtubule-associated protein 1A/1B-light chain 3 (LC3A/B) showed lower immunoreactivity at 21 °C, with no temporal variation. Ultrastructural analysis revealed preserved hepatocyte integrity at both temperatures and abundant cytoplasmic dense bodies consistent with autolysosomal structures, which increased over time. Overall, a realistic warming scenario altered growth dynamics and cellular morphology. Further, this data reinforces that 3D fish liver models are viable alternative systems for assessing climate-driven effects.

Ant‐Mediated Ecosystem Functions Along a Tropical Elevational Gradient - Chaim J. Lasmar; Mariana A. Rabelo; Tom R. Bishop; Catherine L. Parr; Icaro Wilker; Antônio C. M. Queiroz; Mayara M. G. Imata; Guilherme P. Alves; Gabriela B. Nascimento; Vanessa L. Resende; Rodrigo M. Feitosa; Carla R. Ribas (Journal of Biogeography, 2026)
Aim Elevational gradients are excellent systems to study biodiversity variation, yet the ecosystem functions performed by animals along these gradients are poorly understood. We assessed tropical elevational patterns of ant‐mediated seed removal, insect predation and the phylogenetic diversity of the local ant assemblages performing these functions as well as the effects of climate and productivity. Location Southeast Brazil, Atlantic Forest. Taxon Ants. Methods We sampled ant‐mediated seed removal and insect predation across 20 transects, comprising an elevational gradient of approximately from 0 to 1000 m a.s.l. We extracted standardized phylogenetic metrics of the assemblages performing the functions: Faith's PD (SES PD), mean pairwise distance (SES MPD), and mean nearest taxon distance (SES MNTD). We also extracted climatic and productivity predictors for each transect. We then used generalized additive models to evaluate the responses of each function and their phylogenetic metrics along elevation, climate and NPP. Results Both ant‐mediated functions and species richness decreased along the elevational gradient, peaking at the same mid‐elevation, while SES MNTD increased linearly with elevation. Both ant‐mediated functions were positively correlated with temperature. However, we found that phylogenetic richness (SES PD) was lower in warmer and more seasonal environments, while phylogenetic divergence (SES MNTD) was also lower in warmer but drier environments. Main Conclusions Our findings suggest that diversity is linked to ecosystem functioning along the elevational gradient. Although high‐elevation assemblages may show greater evolutionary potential because they comprise distantly related taxa, ecosystem functions might be more vulnerable to species loss. Additionally, we highlighted that although elevated temperatures may boost ecosystem functioning in the short term, when acting together with increased seasonality and dryness, as expected under climate change, they could heighten the vulnerability of the ants responsible for these functions, potentially compromising ecosystem resistance and resilience in a changing world.

Tissue damage to clownfish (Amphiprion ocellaris) exposed to different concentrations of nanoparticles of a stable polymer (polystyrene) compared to a biodegradable polymer (poly(lactic acid)) - Camila Gomes de Oliveira; Túlio Pacheco Boaventura; Fábio Aremil Costa dos Santos; André de Sena Souza; Sidney dos Santos Silva; Luisa Araujo Alves Silva; Camila Silva Brey Gil; Ronald Kennedy Luz; Rodrigo Lambert Oréfice (Marine Pollution Bulletin, 2026)

Laboratory and field evaluation of LAMP assays for canine visceral leishmaniasis diagnosis - Geovanna Vioti; João Augusto Franco Leonel; Trícia Maria Ferreira de Sousa Oliveira; Diogo Tiago da Silva; Maria Luana Alves; Andrea Cristina Higa Nakaghi; Lara Borges Keid; Luiz Ricardo Paes de Barros Cortez; Thayssa Duarte Costa; Rodrigo Martins Soares (Research in Veterinary Science, 2026)

Soil-relief-parent material relationship in a sequence of migmatite and gneiss in the semiarid Cariri region - Emanuel da Costa Cavalcante; Rodrigo Santana Macedo; Robson Vinício dos Santos; João Henrique Melo; Marcelo Metri Corrêa; Kalline de Almeida Alves Carneiro; Gabriel Ramatis Pugliese Andrade; Flávio Pereira de Oliveira; Antônio Augusto Sousa; Jean-Thomas Cornélis; Milton César Costa Campos (Geoderma Regional, 2026)

Paternal exposure to low-dose N-nitrosodimethylamine (NDMA) induces intergenerational alterations in the prostatic microenvironment of rats - Karen Gabriela Favaro de Souza; Gabrielle Chalupa Faria; Débora Hipólito Quadreli; Ivana Regina da Costa; Bárbara Campos Jorge; Lívia Trippe Nagaoka; Julia Stein; Vanessa Aguiar Rocha; Arielle Cristina Arena; Wellerson Rodrigo Scarano; Glaura Scantamburlo Alves Fernandes (Food and Chemical Toxicology, 2026)

Influence of temperature and pressing time on the properties of medium density fiberboards made from Pinus taeda L. - Alexsandro Bayestorff da Cunha; Joelson Lima Ferreira; Tarcisio Francisco de Camargo; Rodrigo Figueiredo Terezo; Camila Alves Corrêa; Natalia Durigon Melo; Martha Andreia Brand; Polliana D’Angelo Rios (Journal of the Indian Academy of Wood Science, 2026)

Commercial graphene oxides show distinct suitability for silver-nanocomposite formation and antibiofilm activity and cytocompatibility - Thamyres Freire da Silva; Francisco Fábio Pereira de Souza; Thiago Alves de Moura; Luciano Ferreira de Almeida; Maria Rosiene Antunes Arcanjo; Antônio Gomes de Souza Filho; Adriano Lincoln Albuquerque Mattos; Juan Antonio Cecilia; Enrique Rodriguez-Castellon; Henry Kobs; Andreia Fonseca de Faria; Maria Kelva do Carmo; et al. (In vitro models, 2026)

Impact of Solubilized Mannan Oligosaccharide Supplementation on Growth Performance, Digestive Health, Stress Resistance, and Economic Efficiency in Pacific White Shrimp (Penaeus vannamei) Raised in an Intensive Synbiotic System - Danielle Alves da Silva; Flávia Abreu Everton; Gisely Karla de Almeida Costa; Suzianny Maria Bezerra Cabral da Silva; Fernando Leandro dos Santos; Rodrigo Antônio Ponce de Leon Ferreira de Carvalho; Giovani Sampaio Gonçalves; João Fernando Albers Koch; Luis Otavio Brito (Fishes, 2026)
The present study investigated how dietary inclusion of solubilized mannan oligosaccharide (MOS) influences growth performance, digestive health, stress resilience, and production profitability in Pacific white shrimp (Penaeus vannamei) reared under intensive synbiotic conditions. Juveniles averaging 3.00 ± 0.04 g were stocked at 100 shrimp m−2 and fed experimental diets containing 0 (control), 1.0, 2.0, or 4.0 g kg−1 MOS for 60 days. Shrimp receiving 1.0 g kg−1 MOS showed higher growth rate, improved feed conversion, and greater final body weight than the control (p

Biogeography of living coccolithophores in the Southeast Pacific: patterns and drivers of Gephyrocapsa spp. diversity - Francisco Díaz-Rosas; Sebastián Cornejo-Guzmán; Rodrigo Torres; Eduardo Menschel; Samuel Hormazabal; Catharina Alves-de-Souza; Peter von Dassow (Progress in Oceanography, 2026)

From maleic to succinic acid: Electrochemical reduction as a game-changer for green electro-refinery schemes - Suelya da S. Mendonça de Paiva; Rainy Alves de Sousa; Raúl García-Cervillla; Jussara C. Cardozo; Carlos A. Martínez-Huitle; Elisama V. Dos Santos; Justo Lobato; Manuel A. Rodrigo (Journal of Cleaner Production, 2026)

Drugs in paradise: caffeine, cocaine, and painkillers detected in sharks from The Bahamas - Natascha Wosnick; Mónica Alejandra Herrera Agudelo; Carolina Turnes Pasini Deolindo; Rodrigo Hoff; Luan Valdemiro Alves de Oliveira; Paulina Andrea Bahamonde Cardena; Renata Daldin Leite; Patricia Charvet; Rachel Ann Hauser-Davis; Enrico Mendes Saggioro (Environmental Pollution, 2026)

Marine monitoring using UAVs: A bibliometric and systematic review from 2022 to 2025 addressing macroalgae and organic waste in marine environment - Mariana T. Moraes; Michele O. Alves; Mayara Amario; Rodrigo Moulin Ribeiro Pierott; Mohammad K. Najjar; Estevão Freire; Assed N. Haddad (Estuarine, Coastal and Shelf Science, 2026)

Stage-specific expression of immune-related redox metabolism genes in Rhipicephalus (Boophilus) microplus following Theileria equi infection - Carla Alves Rabello; Karina Cristina Paes Galdino; Patrícia Gonzaga Paulino; Nelson da Silva Meireles; Pamella Pryscila de Alvarenga Bissoli Maciel de Lima; Laís Feliciano de Souza; Carlos Luiz Massard; Maristela Peckle; Rodrigo Maciel da Costa Godinho; Daniel da Silva Guedes Junior; Júlio César Ferraz Jacob; Huarrisson Azevedo Santos (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

Reproductive efficiency of Nelore (Bos indicus) cows submitted to conventional resynchronization or ReBreed21 programs - Mirela Balistrieri; Tainá L.P. Azevedo; Paula R. Cortat; Marcos H.A. Colli; Lucas O. e Silva; Carlos E.C. Consentini; Rodrigo L.O.R. Alves; José R. Gonçalves; Alexandre B. Prata; Roberto Sartori (Theriogenology, 2026)

Prebiotics attenuate depressive-like behavior, neuroinflammation and synaptic plasticity in Parkinson’s disease by modulating butyrate-producing gut bacteria - Ingrid Prata de Mendonça; Rodrigo Soares da Silva; Igor Henrique Rodrigues de Paiva; Belmira Lara da S. A. Costa; Karla Patrícia de Sousa Barbosa Teixeira; José Roberto Botelho de Souza; Christina Alves Peixoto (Inflammopharmacology, 2026)
Parkinson’s disease (PD) remains a challenging disease for treatment, which is usually polypharmacological. In addition to motor symptoms, non-motor symptoms such as depression are present in approximately 40% of patients, contributing to the loss of quality of life. In the last two decades, a growing body of evidence has emerged regarding the involvement of the microbiota-gut-brain axis in both PD and depression. Fructooligosaccharides (FOS) and galactooligosaccharides (GOS) are prebiotic fibers that can be fermented by the gut microbiota, which produce metabolites called short-chain fatty acids (SCFAs), whose effects can contribute to improvement in neurodegenerative and psychiatric conditions. This study analyzed the effects of FOS and GOS administration in a rotenone-induced PD model and demonstrated a relief of motor symptoms and depressive-like behavior, followed by an increase of brain serotonin and its respective receptor (SERT). FOS and GOS treatment also led to an increase in SCFAs-producing gut bacteria with significantly higher levels of serum and brain butyrate. Furthermore, in the intestine, prebiotics reduced the accumulation of α-synuclein, decreased inflammation, and improved the expression of zonula occludens and occludin. FOS and GOS also attenuated the loss of dopaminergic neurons and reduced neuroinflammation by decreasing α-synuclein, IBA-1, GFAP, iNOS, p-NFkB, and IL1-β levels in the substantia nigra and prefrontal cortex. In addition, these prebiotics improved neuroplasticity by promoting the expression of butyrate receptors (GPR43 and GPR109), BDNF, p-CREB, and synaptic protein PSD-95. In conclusion, FOS and GOS administration attenuatted depressive-like behavior, neuroinflammation, and synaptic plasticity in Parkinson’s disease by modulating butyrate-producing gut bacteria.

ATLANTIC SPATIAL: A dataset of landscape, topographic, hydrological, and anthropogenic metrics for the Atlantic Forest - Maurício Humberto Vancine; Bernardo Brandão Niebuhr; Renata L. Muylaert; Júlia de Oshima; Vinicius Tonetti; Rodrigo Bernardo; Rafael Souza Cruz Alves; Eduardo Miguel Zanette; Victor Casagrande Souza; João Gabriel Ribeiro Giovanelli; John Wesley Ribeiro; Carlos De Angelo; et al. (Ecology, 2026)
Space is one of the main drivers of biodiversity, as it regulates the underlying processes affecting the distribution and dynamics of species and communities. It is a fundamental factor when considering the rapid climate and land cover changes occurring at local and global scales, which are linked to habitat loss and fragmentation, as well as their impacts on biodiversity. The Atlantic Forest of South America is among the world's biodiversity hotspots because of its exceptionally high species richness and endemism. Most of the threats to the Atlantic Forest's biodiversity stem from the expansion of urbanization and industry, extensive agricultural and livestock production, and mining. Here, we provide integrated and fine‐scale spatial information (30‐m resolution) for the entire extent of the Atlantic Forest for the years 2020 to 2022. The spatial data include different vegetation classes (forest, and forest combined with other non‐forest vegetation), the effects of linear structures (roads and railways), and landscape metrics computed at multiple scales (radius buffers—moving window sizes—ranging from 50 to 2500 m, and up to 10 km for some metrics). The dataset comprises the Atlantic Forest delimitation vector and more than 500 rasters, available through a series of thematically grouped files in multiple Zenodo repositories. This data can also be accessed using the R package atlanticr , which we developed to facilitate data retrieval and organization from Zenodo. The dataset includes landscape, topographic, hydrological, and anthropogenic metrics. Landscape metrics were calculated for two vegetation classes—Forest Vegetation (which combined different forest cover classes) and Natural Vegetation (which combined forest and non‐forest cover classes)—as well as for a heterogeneous, multi‐class classification of the landscape (31 land cover classes). The landscape metrics include landscape morphology (classification as matrix, core, edge, corridor, branch, stepping stone, and perforation), fragment area and proportion, patch area and number, edge and core areas and proportions, structural and functional connectivity (for different organisms' gap‐crossing capabilities), distance to and from fragment edges, fragment perimeter and perimeter–area ratio, and landscape diversity (heterogeneity). Topographic metrics include elevation, slope, aspect, curvature, and landform elements (peak, ridge, shoulder, spur, slope, hollow, footslope, valley, pit, and flat). Hydrological metrics comprise potential springs (and their kernel density) and streams (and distance to the nearest feature). Anthropogenic metrics include maps of roads, railways, protected areas, Indigenous territories, and quilombola territories (localities of self‐defined Afro‐Brazilian traditional communities), as well as the distance to each feature. This dataset facilitates the efficient integration of biodiversity and spatially explicit data for the Atlantic Forest, serving as a data source for studies, landscape planning, biodiversity conservation, and forest restoration programs. The data are released under a CC BY‐NC 4.0: Creative Commons Attribution‐Non‐Commercial 4.0 International license and this data paper should be cited when the data are reused.

Time and contamination level dependence of metal bioaccumulation and multibiomarker responses in fish: implications for biomonitoring - Paloma Kachel Gusso-Choueri; Rodrigo Brasil Choueri; Luciane Alves Maranho; Aline Vecchio Alves; Caio Rodrigues Nobre; Gabriela Pustiglione Marinsek; Renata de Britto Mari; Tailisi Hoppe Trevizani; Rubens Cesar Lopes Figueira; Denis Moledo de Souza Abessa (Environmental Monitoring and Assessment, 2026)
This study evaluated how different levels of sediment metal contamination (ranging from below to above toxicity thresholds) and exposure durations (3–14 days) influence metal bioaccumulation and biomarker responses in fish under estuarine conditions. Using an integrated biomarker approach, the relationships among environmental contamination, metal accumulation, and fish health were examined to improve biomonitoring strategies. At the highest contamination level, 100% mortality was observed. Under low contamination, fish eliminated excess Cu, Zn, and Hg, whereas moderate contamination resulted in progressive accumulation of Cu and Zn; Pb accumulated under both exposure levels. Early biomarker responses included decreased GSH, inhibited GPx, increased lipid peroxidation, histopathological liver lesions, and neurotoxicity, followed by partial recovery. DNA damage increased over time and across contamination levels, likely due to impaired antioxidant defenses and/or direct metal–DNA interactions. Histopathological alterations were more strongly associated with sediment contamination than with tissue concentrations, indicating that body burdens may not fully represent exposure. GSH depletion and DNA damage were the most consistent biomarkers, whereas LPO and histopathology were sensitive primarily at early exposure stages. These findings reinforce the importance of considering both exposure duration and contamination level when interpreting biomarker responses and highlight the limitations of short-term or single-biomarker assessments. Biological effects detected at low to moderate contamination support the need for more precautionary sediment-quality thresholds. Overall, integrating biochemical, physiological, and histological biomarkers provides early detection of sublethal effects and a comprehensive assessment of ecosystem health. Consequently, a multibiomarker framework represents a powerful tool to strengthen the monitoring, evaluation, and management of aquatic environmental quality.

Soil quality and soybean yield responses to occasional subsoiling and crop system diversification in a consolidated no-tillage system - Cristiano Alves da Silva; Rodrigo Arroyo Garcia; Michely Tomazi; Elaine Reis Pinheiro Lourente; Sérgio Augusto Rodrigues; Dirceu Maximino Fernandes (Soil and Tillage Research, 2026)

Assessing Urban Ditches for Tracking SARS-CoV-2 in Low Sanitation Areas in Southeastern Brazil - Regina Keller; Gizely Azevedo Costa; Paola de Avelar Carpinetti; Ricardo Franci Gonçalves; Mariane Vedovatti Monfardini Sagrillo; Rodrigo Nunes Oss; Danielsan de Jesus Dias; Isabella Balarini de Azevedo Chaiben; Laila de Oliveira Vaz Oliveira; Rodrigo Pratte; Alice Barros Câmara; Sérvio Túlio Alves Cassini; et al. (Food and Environmental Virology, 2026)
Several studies investigated the presence of SARS-CoV-2 in water samples and raw urban wastewater collected from urban sewage treatment plants (STPs) during the COVID-19 pandemic and correlated viral load and epidemiological data. However, limited information is available regarding the potential of urban ditches as sampling sites for epidemiological surveillance. This study aimed to detect SARS-CoV-2 RNA in urban ditches and evaluate its correlation with epidemiological data. A total of 168 samples were collected from January 2021 to February 2022 in three urban ditches and two STPs in the metropolitan region of Vitória, Espírito Santo (ES). Physicochemical and microbiological water quality parameters were analyzed, and SARS-CoV-2 RNA was detected using a TaqMan RT-qPCR system. SARS-CoV-2 was detected in 145/168 of the samples, with 87.2% (75/86) found in the urban ditches and 85.3% (70/82) in the STPs. The viral load in the three urban ditches ranged from 1.59 × 10 4 to 2.56 × 10 4 genome copies/litre (GC/L) while in the two STPs, it ranged from 7.79 × 10 3 to 1.26 × 10 4 GC/L. A moderate to strong positive correlation was observed between viral load and confirmed COVID-19 cases, particularly for samples collected from urban ditches (ditch 1, r = 0.58; ditch 2, r = 0.78; ditch 3, r = 0.86). The results indicate greater correlation of SARS-CoV-2 RNA concentration in ditches of low sanitation areas as compared with STPs, showing that ditches could be an important and equivalent sampling point for viral epidemiological studies.

Mammal defaunation leads to biotic homogenization of plant communities in tropical rainforests - Luiz Guilherme dos Santos Ribas; Nacho Villar; Valesca Zipparro; Sérgio Nazareth; Yuri Souza; Carlos Rodrigo Brocardo; Gabriela Schmaedecke; Luana Hortenci; Rafael Souza Cruz Alves; Mauro Galetti (Ecology, 2026)
Biotic homogenization is the process in which species communities become increasingly similar across different regions over time. This phenomenon has substantial ecological, evolutionary, and economic implications, primarily driven by human activities such as habitat destruction, invasive species introduction, and climate change. An underexplored driver of biotic homogenization is defaunation, particularly the loss or population decline of large herbivorous mammals and its consequences on plant communities. In this study, we examined how defaunation of medium‐ to large‐sized mammals, such as tapirs and peccaries, affects taxonomic biotic homogenization in seedling and sapling communities in tropical rainforests of South America. Using data from a 13‐year mammal‐exclosure experiment across four forest sites in the Brazilian Atlantic Forest, we investigated the effects of defaunation on both alpha and beta diversity to understand how it might contribute to biotic homogenization. Our results indicate that defaunation significantly increased alpha diversity in exclusion plots over time, contrary to expectations, with more pronounced effects at forest sites hosting more complete mammal assemblies, that is, with greater mammal abundance and diversity. In contrast, beta diversity decreased as exclusion treatments led to more spatially homogeneous plant communities, particularly at the site where exclusion treatment prevents access to the plant community by the most complete mammal assembly. This homogenization was driven by reduced species turnover and the dominance of a few plant species that thrive in the absence of mammal herbivores, including a palm Euterpe edulis , a bamboo Merostachys neesii , and a fern Polybotrya cylindrica . These findings suggest that the removal of medium‐ to large‐sized mammal herbivores can lead to both increased local species richness and decreased spatial heterogeneity, reshaping plant community structure across tropical forest landscapes. Our study highlights the critical role of large‐bodied herbivores in maintaining biodiversity at multiple scales and underscores the ecological consequences of their functional loss. This work provides essential insights for conservation efforts aimed at mitigating the impacts of defaunation and preserving the resilience of tropical forest ecosystems, positioning defaunation as a significant anthropogenic driver of biotic homogenization.

Exploring the chemical composition and functional properties of essential oils: insights into antioxidant, antibacterial, and anti-SARS-CoV-2 activities - Pedro Henrique Santos; Jéssica de Souza Marciano; Daniel J. da Silva; Paulo Henrique Camani; Greiciele Ferreira; Adriana Feliciano Alves Duran; Lívia de Moraes Bomediano Camillo; Rodrigo de Freitas Bueno; Derval dos Santos Rosa (South African Journal of Botany, 2026)

The recovery of forest structure 30 years after timber harvesting: a comparison of harvesting methods using field inventories and drone-based LiDAR data - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2026)

Enhanced H2O2 electrogeneration for simultaneous degradation of multiple pharmaceuticals and validation in real water using UVC-assisted processes - Raul José Alves Felisardo; Florymar Escalona Durán; Carlos Henrique Magalhães Fernandes; Géssica de Oliveira Santiago Santos; Renata Colombo; Manuel Andrés Rodrigo Rodrigo; Marcos Roberto de Vasconcelos Lanza (Chemical Engineering Journal, 2026)

Ozone effects in coffee (Coffea arabica L.) plants: Cultivar-specific responses and risk assessment - Barbara Baesso Moura; Marisa Domingos; Emerson Alves da Silva; Jacopo Manzini; Elena Marra; Leonardo Lazzara; Rodrigo Fazani Esteves Sanches; Elena Paoletti; Yasutomo Hoshika (Atmospheric Pollution Research, 2026)

Spectroscopic exploration of mode of binding of ct DNA and BSA with acridone alkaloids isolated from Zanthoxylum leprieurii (Rutaceae) - Whistler Lucain Dibahteu Tankoua; Ernestine Zondegoumba T. Nkwengoua; Soh Desiré; Olivier Ndogo Eteme; Emmanuella Marthe Tchana Satchet; Rodrigo Santos A. de Araujo; Anuraj Nayarisseri; Maria do Carmo Alves de Lima; Thiago Mendonça de Aquino; Nyassé Barthélémy; Francisco J. B. Mendonça-Junior (Natural Product Research, 2026)

Deep Learning-Based Classification of Temporal Stages of AT8-Labeled Tau Pathology After Experimental Traumatic Brain Injury - Guilherme José de Antunes e Sousa; Rodrigo Afonso Sá; Marcos António Spínola Monteiro Gomes; George A. Edwards; Ines Moreno-González; Ricardo José Alves de Sousa (Neuroinformatics, 2026)
Tauopathies are characterised by a progressive accumulation of hyperphosphorylated tau. However, early and intermediate stages remain challenging to quantify due to subtle and heterogeneous morphological characteristics. This study evaluates a deep learning framework for classifying multiple temporal stages of tauopathy progression using AT8 (anti-phospho-tau antibody)-stained cortical micrographs in a controlled traumatic brain injury mouse model – an underexplored application. Three convolutional neural network (CNN) architectures were examined: a custom CNN and two transfer-learning models (InceptionV3 and DenseNet). Images were grouped into four post-injury stages: 1 day, 1 week, 1 month and 3 months. Preprocessing included normalisation, augmentation and oversampling to address imbalance. Performance was assessed using stratified k-fold cross-validation with accuracy, macro-F1, per-class F1, and one-vs-rest area under the receiver operating characteristic curve (AUC). DenseNet achieved the best overall performance (accuracy = 70.9%, macro-F1 = 0.68) with strong discrimination for the 1-week stage (F1 = 0.95). All models showed limited separability in the earliest post-injury stage (1 day), while intermediate to late stages (1–3 months) exhibited partial overlap, consistent with the progressive nature of tau accumulation. These results indicate that deep learning, particularly transfer learning, offers a scalable approach for automated temporal staging of tauopathy in preclinical histology. Although the results are based on internal cross-validation without independent animal-level identifiers or external cohorts, the proposed framework provides a reliable foundation for incorporating CNN-based analysis into digital neuropathology workflows. Larger multi-centre datasets and slide-level modelling will be required to assess generalisation and support applications in early detection, longitudinal tracking, and treatment evaluation of tau-related neurodegeneration.

Cetaceans Change Their Acoustic Behavior During the Airgun Noise of Seismic Surveys - Israel Maciel; Rodrigo Tardin; Sergio Carvalho Moreira; Gabriel Melo-Santos; Guilherme Maricato; Maria Alice S. Alves (Journal of Marine Science and Engineering, 2026)
Seismic surveys introduce high levels of noise into the soundscape. Thus, a major concern is the effect of these noise levels on animal communication, especially for species with high hearing acuity, such as cetaceans. We evaluated the effects of airgun pulses of seismic surveys on the acoustic behavior of humpback whales (Megaptera novaeangliae) and pantropical spotted dolphins (Stenella attenuata) in the two most important basins for oil and gas off Brazil. We detect the presence of airgun pulses and measure sound pressure levels (SPL) to evaluate whether SPL changed the acoustic parameters of cetacean vocalizations. Airgun pulses increased the SPL by 17%. This changes acoustic parameters differently: whales reduced call frequency and duration, while dolphins increased these parameters. In both cases, responses may be related to physiological limitations in sound modulation of each species. This was the first report on the impacts of seismic surveys on cetaceans’ communications in Brazil and the first for the pantropical spotted dolphin on this topic in the world. Impacts vary with the frequency and duration of emissions, indicating species-specific acoustic responses that depend on airgun noise characteristics. Whales cannot make efficient adjustments at higher or lower frequencies, and dolphins cannot adjust at lower frequencies. These results are important for discussing the effects of airgun noise on cetacean communication.

PAH pollution in water and blue mussels (Mytilus edulis) along the northern Portuguese Atlantic Coast: Evaluation of ecological and human cancer risks - Ana Margarida Esteves; Rodrigo F. Alves; Eduardo Rocha; Maria João Rocha (Marine Pollution Bulletin, 2026)

Evaluation of hair samples for PCR detection of Leishmania infantum in dogs - Geovanna Vioti; João Augusto Franco Leonel; Trícia Maria Ferreira de Sousa Oliveira; Diogo Tiago da Silva; Maria Luana Alves; Andrea Cristina Higa Nakaghi; Lara Borges Keid; Rodrigo Martins Soares (Research in Veterinary Science, 2026)

Seasonal patterns and atmospheric modulators of erythemal UV radiation in a sensitive region of the Brazilian Amazon: Implications for environmental health risk assessment - Pericles Vale Alves; Vandoir Bourscheidt; Damaris Kirsch Pinheiro; Rodrigo Martins Moreira; Marcos André Braz Vaz; Mônica Santos; Marcos Antônio Lima Moura; Carlos Alexandre Santos Querino; Paula Regina Humbelino de Melo; Maria Adriana Moreira (Remote Sensing Applications: Society and Environment, 2026)

Larvicidal efficacy of Varronia curassavica leaf phytochemicals against Aedes aegypti: anatomical, histological and cytotoxic analyses - Marcela Rezende Cordeiro; Saulo Pireda; Maria Aparecida Aride Bertonceli; Thalya Soares Ribeiro Nogueira; Nicolly Lopes Bautz; Rodrigo Barbosa Braga Feitoza; Felipe Figueirôa Moreira; Ivo José Curcino Vieira; Carlos Roberto Ribeiro Matos; Raimundo Braz-Filho; Sergio Henrique Seabra; Francisco José Alves Lemos; et al. (Pesticide Biochemistry and Physiology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Ants as Flower Visitors: Diversity and Network Structure Assessed for the First Time in the Atlantic Forest of Southern Brazil - Ana Carolina Alves Neundorf; Alessandra Mikich; Rodrigo Feitosa; Natalia Ladino; Vitória Ramos Macedo; Sandra Bos Mikich (Neotropical Entomology, 2025)

The chemistry of hydrogen peroxide: Applications and analytical techniques for detection in water and food matrices - Luísa Faria Monteiro Mazzini; Tatianny de Araujo Andrade; Alana Alves Rodrigues; Rodrigo Silva de Oliveira; Kleryton Luiz Alves de Oliveira; Renata Pereira Lopes Moreira (Food Chemistry, 2025)

The invisible impact of tourism: organic UV filters in the coastal ecosystem of a remote Atlantic island - Eva Íñiguez; Rodrigo Pires da Silva; Sarah Montesdeoca-Esponda; Elli Dimou; Filipe Alves; Manfred Kaufmann; Ana Dinis; Nereida Cordeiro (Environmental Research, 2025)

Climatic decoupling of tree floras under climate change in the central region of South America - Marcelo Leandro Bueno; Rodrigo Cyrino Rivaben; Arnildo Pott; Geraldo Alves Damasceno; Larissa de Oliveira Cardoso; Eliane Vieira; Jefferson Matheus Barros Ozório; Vanessa Pontara (Theoretical and Applied Climatology, 2025)

Early selection in Eucalyptus urophylla progenies under water stress conditions in tropical regions - Franciele Alves Menês; Paulo Henrique Müller da Silva; Guilherme Nichele da Rocha; Andrei Caíque Pires Nunes; Rodrigo Andrade de Furlan; Cristiano Moraes (New Forests, 2025)

Effects of Chronic Photobiomodulation with Transcranial Near-Infrared Laser on Seizure Frequency and Brain Metabolomics of Rats with Pilocarpine-Induced Seizures - Fabrizio dos Santos Cardoso; Ricardo Mario Arida; Eduardo Alves da Silva; Ana Carolina Ribeiro de Oliveira; Wagner Ferreira dos Santos; Rodrigo Álvaro Brandão Lopes-Martins; Francisco Gonzalez-Lima; Norberto Cysne Coimbra; Sérgio Gomes da Silva (Molecular Neurobiology, 2025)
Epilepsy is a chronic brain disorder characterized by abnormal and highly synchronous activity of neuronal cells. This condition is often associated with neuronal hyperexcitability and metabolic imbalances in regions such as the neocortex and archicortex (hippocampus). Pharmacological treatment with antiepileptic drugs has been essential in most cases. However, some patients continue to experience seizures despite medication. Consequently, the search for alternative treatments and new therapeutic interventions has garnered significant interest within the medical community. Among these, photobiomodulation (PBM) shows great promise, particularly due to its cerebral and neuroprotective effects. We evaluated and compared the seizure frequency and the neocortical and hippocampal metabolomic profiles of pilocarpine-induced epileptic rats exposed to chronic transcranial photobiomodulation treatment (30 days of treatment) with an 810-nm, 100-mW laser. Our data show that PBM treatment significantly reduced the seizure frequency in rats with pilocarpine-induced seizures. Additionally, significant changes were observed in the metabolomic profiles of the neocortex and hippocampus. In the neocortex, the treatment reduced metabolic pathways associated with excitotoxicity and oxidative stress. In the hippocampus, an increase in phenylalanine concentration was detected. In addition, the reduction in the number of seizures in laser-treated rats with pilocarpine-induced seizures was correlated with lower neocortical lysine concentration. Taken together, our findings indicate that transcranial PBM prevents the increase in seizure frequency in rats with epilepsy and modulates the brain metabolic pathways of epileptic rats.

Acute toxicity and hematological effects of a silver nanoparticle–Terminalia catappa nanocomposite in juvenile tambaqui (Colossoma macropomum) - Juliana Oliveira Meneses; Fernanda dos Santos Cunha; Joel Artur Rodrigues Dias; Natalino da Costa Sousa; Márcia Valéria Silva do Couto; Higo Andrade Abe; Ana Flávia Santos da Cunha; Juliana Cordeiro Cardoso; Luiz Pereira da Costa; Lumar Lucena Alves; Peterson Emmanuel Guimarães Paixão; Rodrigo Yudi Fujimoto (Aquaculture International, 2025)

Marine protected areas miss key habitats of Bryde's whales and bottlenose dolphins exposed to anthropogenic stressors - Guilherme Maricato; Rodrigo Tardin; Clinton N. Jenkins; Fábio G. Daura-Jorge; Márcia H. Engel; Liliane Lodi; Israel Maciel; Milton C.C. Marcondes; Gabriel Melo-Santos; Lucas Milmann; Maria Alice S. Alves (Marine Pollution Bulletin, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Chronic iron overload disrupts the reproductive tract and leads to infertility: From a clinical case report to the experimental study of reproduction in female mice - Charles S. da Costa; Vinícius Bermond Marques; Jandinay Mageski; Paulo Caleb J.L. Santos; Rodrigo Alves Faria; Isabela V. Sarmento; Poliana Borges de Oliveira; Maira Krause; Maria Tereza W. D Carneiro; Leonardo dos Santos; Jones B. Graceli (Reproductive Toxicology, 2025)

Extract rich in polyprenylated benzophenones from Brazilian red propolis: obtaining, analytical characterization and in vitro evaluation against breast cancer lines - Rodrigo Cassio Sola Veneziani; Raquel Alves dos Santos; Loren Monielly Pires; Laisla Rodrigues Figueiredo; Renata Faleiros; Karolinne Beloti Silva; Mario Ferreira Conceição Santosa; Jairo Kenupp Bastos (Phytochemistry Letters, 2025)

Natural regeneration responses of tree species at the end of the first timber harvesting cycle in the Eastern Amazon - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2025)

N-acyl hydrazone derivatives reduce pro-inflammatory cytokines, iNOS and COX-2 in acute lung inflammation model - Katharina Rodrigues de Lima Porto Ramos; Jéssica de Andrade Gomes Silva; Rayane Siqueira de Sousa; Elizabeth Fernanda de Oliveira Borba; Marília Grasielly de Farias Silva; Sonaly Lima Albino; Silvana Tavares Paz; Rodrigo Soares da Silva; Christina Alves Peixoto; Vanda Lúcia dos Santos; Ricardo Olímpio Moura; Teresinha Gonçalves da Silva (Chemico-Biological Interactions, 2025)

Reproductive and agonistic interactions mediated by multimodal signals of a Neotropical torrent frog - Guilherme Augusto-Alves; Natália Aranha; Luís Felipe Toledo; Rogério Pereira Bastos; Rodrigo Lingnau (acta ethologica, 2025)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a feedlot system submitted or not to ovulation induction strategies prior to a timed-artificial insemination treatment regimen - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Oseias P. Santos; Andrés A.C. Narváez; Leandro D. da Cunha; Rafael A. Braz; Maria E.R. e Silva; Rodrigo Brüner; Leonardo F. Melo; Roberto Sartori (Theriogenology, 2025)

Sex-Dependent Changes in the Gene Expression of UPR-Associated Calcium-Binding Proteins in the STZ–Induced Model of Alzheimer’s Disease - Bruna Schultz; Larissa Bobermin; Leonardo Menezes; Vitor Gayger-Dias; Vanessa-Fernanda Da Silva; Jéssica Taday; Joelma Alves; Francine Tramontina; Caroline Zanotto; Carla Dalmaz; Marina Concli Leite; Rodrigo Bainy Leal; et al. (Molecular Neurobiology, 2025)

Paraprobiotics Mitigate Inflammation and Anxiety-Like Behavior in a Lipopolysaccharide-Induced Mouse Model - Monique Michels; Gabriel Fernandes Alves Jesus; Emily Córneo; Luana Bezerra Rocha; Rodrigo Dias; Ana Paula Lorenzen Voytena; Marina Piola Rossetto; Fernanda Ramlov; Felipe Dal-Pizzol; Ana Paula Pesarico (Current Microbiology, 2025)

A novel nanocatalyst of the multi-walled carbon nanotubes decorated with niobium pentoxide for the Eriochrome black T dye degradation - Claudir Gabriel Kaufmann; Daniel Moro Druzian; William Leonardo da Silva; Rubia Young Sun Zampiva; Marco Rossi; Giovani Pavoski; Denise Crocce Romano Espinosa; Annelise Kopp Alves; Carlos Pérez Bergmann; Cristiano Rodrigo Bohn Rhoden; Sergio Roberto Mortari (Environmental Science and Pollution Research, 2025)

VOC removal on activated biochar prepared from the invasive aquatic plant Eichhornia crassipes for air decontamination by temperature swing adsorption process - Rodrigo Santos Gonzaga Menezes; José Luiz Cunha Cordeiro; Robson Carlos de Andrade; Humberto Polli; Mauricio Brandão dos Santos; Fernanda Teixeira Cruz; Artur José Santos Mascarenhas; Heloysa Martins Carvalho Andrade; Raildo Alves Fiuza-Junior (Environmental Science and Pollution Research, 2025)

Analysis of the ecotoxicity of waste generated in a laundry in the textile center of the Agreste region of Pernambuco using zebrafish (Danio rerio) as a bioindicator - Paula Raíza Alves Cavalcante; Jadson Freitas da Silva; Renatta Priscila Ferreira Silva; Matheus Victor Viana de Melo; Maria Letícia Santos Carnaúba da Silva; Maria Eduarda Borges de Almeida; Samara da Silva Gomes; Yuri Mateus Lima de Albuquerque; Rodrigo Cândido Passos da Silva; Pabyton Gonçalves Cadena; Rosângela Gomes Tavares (Environmental Science and Pollution Research, 2025)

Translational insights into statin-induced myotoxicity: Differential impact of lipophilic and hydrophilic statins on iPSC-derived skeletal muscle cells from patients with familial hypercholesterolemia - Raul Hernandes Bortolin; Felipe de Souza Leite; Andre Ducati Luchessi; Joyce Esposito; Igor Neves Barbosa; Renata Caroline Costa de Freitas; Abhijeet Rajendra Sonawane; Sasha Anna Singh; Elena Aikawa; Kayque Alves Telles-Silva; Thiago Dominguez Crespo Hirata; Antonia Pereira Rosa Neta; et al. (Toxicology, 2025)

Maternal exposure to phthalates and nanoplastics, isolated or combined: Impacts on placental structure, development, and antioxidant defense as a trigger for maternal-fetal adversities - Natália Magosso; Patrick Vieira Souza; Mirella Franco Moreira; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Victória Cristina Pinha; Gabriel Aquino Maia; Vinícius Luís Rocha S. Maria; Luisa Annibal Barata; Giovanna Fachetti Frigoli; Glaura Scantamburlo Alves Fernandes; Arielle Cristina Arena; et al. (Reproductive Toxicology, 2025)

Photobiomodulation presents an anti-inflammatory effect, reflecting on the expression of receptors related to the pain process in a collagenase-induced tendinitis experimental model - Yose Marie Elizabeth e Silva; Patrícia de Viveiros Tavares Alves; Rachel Bharbara Maccheronio Dalmaso; Ana Paula Ligeiro de Oliveira; Cinthya Cosme Gutierrez Duran; José Antônio Silva Júnior; Stella Regina Zamuner; Maria Fernanda de Souza Setubal Destro; Rebeca Boltes Cecatto; Rodrigo Álvaro Brandão Lopes Martins; Richard Eloin Liebano; Rodrigo Labat Marcos (Journal of Photochemistry and Photobiology B: Biology, 2025)

Photodegradation and Adsorption Using a Fiber-based MIL88A/MoS2 for organic contaminant removal - Ana Laura M.M. Alves; Rodrigo Schneider; Rafaela S. Andre; Daniel S. Correa (Journal of Cleaner Production, 2025)

Artificial intelligence-based optimization of the WEEE reverse chain in São Paulo − Brazil to promote economic, environmental and social benefits - Geraldo C.de Oliveira Neto; Rodrigo Neri Bueno da Silva; Gustavo Araújo Lima; Sidnei Alves de Araújo; Peterson Adriano Belan; Denilson Carvalho; Cecília M.V.B. Almeida (Journal of Cleaner Production, 2025)

Basalt rock dust as a soil remineralizer in upland rice grown in tropical soils: residual effects on soil fertility, Si availability, and leaf anatomy - Mariana de Carvalho Ribeiro; Aline Redondo Martins; Rodrigo Silva Alves; Luís Gustavo Frediani Lessa; Hamilton Seron Pereira; Fernando Shintate Galindo; Marcelo Carvalho Minhoto Teixeira Filho; Cassio Hamilton Abreu–Junior; Arun Dilipkumar Jani; Gian Franco Capra; Antonio Ganga; Thiago Assis Rodrigues Nogueira (Journal of Cleaner Production, 2025)

Effects of zinc oxide and monoglyceride blend on intestinal immune, health and microbiota responses of weanling pigs - Ana Lígia Braga Mezzina; Erick Marlon Pereira; Cecília Archangelo Ferreira de Melo; Thallysson Taumaturgo Silva Souza; Matheus Saliba Monteiro; André Pegoraro Poor; Bruno Bracco Donatelli Muro; Caroline Veloso; Flávio de Aguiar Coelho; Rafaella Fernandes Carnevale; Francisco Alves Pereira; Fernanda Mariane dos Santos; et al. (Veterinary Research Communications, 2025)

Metformin Improves Spatial Memory and Reduces Seizure Severity in a Rat Model of Epilepsy and Alzheimer’s Disease comorbidity via PI3K/Akt Signaling Pathway - Suélen Santos Alves; Letícia Rossi; Jose Antonio Cortes de Oliveira; Gabriel Servilha-Menezes; Mariana Grigorio-de-Sant’Ana; Rodrigo Focosi Mazzei; Sebastião Sousa Almeida; Adriano Sebollela; Rui Milton Patrício da Silva Junior; Norberto Garcia-Cairasco (Molecular Neurobiology, 2025)

Phosphate solubilization by filamentous fungi from Antarctic lichens and sediments - Adriely Vital de Souza Silva; Averlane Vieira da Silva; Adeildo Júnior de Oliveira; Rafaela Ferreira da Silva Costa; Rodrigo Paidano Alves; Luiz Henrique Rosa; Valéria Maia de Oliveira; Marcela Eugênia da Silva Cáceres; Janice Gomes Cavalcante; Sabrina Barros Cavalcante; Michel Rodrigo Zambrano Passarini; Aline Cavalcanti de Queiroz; et al. (Extremophiles, 2025)

Exploring pectin and retrograded starch microparticles as carriers for pomegranate peel bio-input in the treatment of Staphylococcus aureus infections - Soraya Dias Saleme; Mikaela Vieira Beloni; Rita Cristina Gonçalves de Melo; Suzana Gonçalves Carvalho; Rodrigo de Almeida Romagna; Elias Werner; Mário Ferreira Conceição Santos; Marlus Chorili; Rodrigo Resende Kitagawa; Juliana Alves Resende; Janaina Cecília Oliveira Villanova (Natural Product Research, 2025)

Adapted methods for helminth detection reveal trematode and nematode infections in terrestrial molluscs of Sergipe State, Brazil - Pedro Dantas Lima; José Luiz de Jesus Santos; Allan Costa Gomes; Rachel Pires Pereira de Carvalho; André Mota Alves; Quezia Machado dos Santos Araújo; João Victor Batista Dos Santos; Luciane Moreno Storti de Melo; Victor Fernando Santana Lima; José Rodrigo Santos Silva (Molluscan Research, 2025)

Reproductive performance of yearling Bos indicus heifers submitted to programs for induction of ovulation prior to a timed-artificial insemination protocol - Ana Luíza M. Lopes; Giselly B. Kolling; Lucas O. e Silva; Rodrigo L.O.R. Alves; Fabiana M. de Assumpção; Suzane K.M. Leite; Akyra Terra; Roger de M. M. Wutke; Antonio C.S. Rezende; José R.S. Rezende; Lainer Leite; Roberto Sartori (Theriogenology, 2025)

Effect of the follicular stage and circulating progesterone concentrations at the beginning of an estradiol/progesterone-based synchronization protocol on profile of gonadotropins and follicle dynamics in beef heifers - Lucas O. e Silva; Patrícia R. Cavalcanti; Rodrigo L.O.R. Alves; Natália P. Folchini; Natália N. Teixeira; Pedro J.L. Monteiro; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2025)

Correction: The impact of genetics and spacing on productivity and energy stock: perspectives on the expansion of Eucalyptus as a biofuel in Brazil - Maria Kely Alves Gomes da Silva; Rosimeire Cavalcante dos Santos; Renato Vinícius Oliveira Castro; Gualter Guenther Costa da Silva; Rodrigo Eiji Hakamada; Daniela Minini; Laise de Jesus dos Santos; Ana Luiza da Silva Lopes-Nunes; Ananias Francisco Dias Júnior (New Forests, 2025)

In vitro anticancer properties of the red seaweed Laurencia (J.V. Lamouroux, 1813): A systematic review - Alexsandra de Morais Martins; Elizabeth Fernanda de Oliveira Borba; Beatriz de Fátima Maia de Santana; Rodrigo Ribeiro Alves Caiana; Ana Carla da Silva; Juliane Bernardi Vasconcelos; Júlio César Ribeiro de Oliveira Farias de Aguiar; Teresinha Gonçalves da Silva; Daniela Maria do Amaral Ferraz Navarro (Algal Research, 2025)

Review of Records and Hypotheses of Giant Tiger Shrimp (Penaeus monodon) Introduction in Brazil - Jhonatas Teixeira Viana; Juliana Oliveira de Freitas; Túlio Ésio Ferreira do Nascimento; Flavio de Almeida Alves-Júnior; Rubens Galdino Feijó; Rodrigo Maggioni (Thalassas: An International Journal of Marine Sciences, 2025)

CoFe2O4/TiO2-Nb2O5 magnetic catalysts synthesized by chemical and physical mixture applied in the reduction of Cr(VI) - Maria Eduarda Kounaris Fuziki; Angelo Marcelo Tusset; Laura Santos Ribas; Elaine Trojan de Paula; Rodrigo Brackmann; Odivaldo Cambraia Alves; Onélia Aparecida Andreo dos Santos; Giane Gonçalves Lenzi (Environmental Science and Pollution Research, 2025)

Space-time mapping of soil organic carbon through remote sensing and machine learning - Bruno dos Anjos Bartsch; Nicolas Augusto Rosin; Jorge Tadeu Fim Rosas; Raul Roberto Poppiel; Fernando Yutaro Makino; Letícia Guadagnin Vogel; Jean Jesus Macedo Novais; Renan Falcioni; Marcelo Rodrigo Alves; José A.M. Demattê (Soil and Tillage Research, 2025)

Associations among production systems, identity aspects, microbiological results and physical-chemical traits as revealed by official analyses of Minas Artisanal Cheese (QMA, Queijo Minas Artesanal) - Amanda Rosário Alvim Santos; Caio Fialho de Freitas; Anderson Carlos Camargo; Rafael Bombachi; Liliane Denize Miranda Menezes; Antônio Fernandes de Carvalho; Sergio Santos de Azevedo; Cinzia Caggia; Rodrigo Alves Barros; Luís Augusto Nero (Food Control, 2025)

Biomarkers responses in the amphipod Tiburonella viscana exposed to the biocide DCOIT and CO2-induced ocean acidification - Wanessa Gentil Mandelli; Aline Vecchio Alves; Fiamma Eugênia Lemos Abreu; Bruna Santana de Morais; Eliete Zanardi-Lamardo; Ítalo Braga Castro; Rodrigo Brasil Choueri; Lucas Buruaem Moreira (Environmental Pollution, 2025)

The impact of genetics and spacing on productivity and energy stock: perspectives on the expansion of Eucalyptus as a biofuel in Brazil - Maria Kely Alves Gomes da Silva; Rosimeire Cavalcante dos Santos; Renato Vinícius Oliveira Castro; Gualter Guenther Costa da Silva; Rodrigo Eiji Hakamada; Daniela Minini; Laise de Jesus dos Santos; Ana Luíza da Silva Lopes-Nunes; Ananias Francisco Dias Júnior (New Forests, 2025)

Feeding rate for newly weaned tambaqui (Colossoma macropomum) juveniles in a recirculating aquaculture system - Bruno José Corecha Fernandes Eiras; Paola Fabiana Fazzi Gomes; Debora Sayumi Doami Melo; Jhonas Warlenson Palheta Nobre; Helen Cristiane Araújo Souza; Marcela Cardoso Sena; Joane Natividade; Igor Hamoy; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; André Luiz Alves de Sá; Rodrigo Takata; et al. (Animal Feed Science and Technology, 2025)

Mass movement hazard assessment of active coastal cliffs (Northeast Brazil) - Melvin Moura Leisner; Davis Pereira de Paula; Rodrigo Guimarães de Carvalho; Frederico de Holanda Bastos; Miguel da Guia Albuquerque; Yan Gurgel Vasconcelos; Deivid Cristian Leal-Alves; Jader Onofre de Morais (Ocean & Coastal Management, 2025)

Primary intracranial squamous cell carcinoma in a mule - João R.C. Brito Junior; Yanca G.S. Soares; Laynaslan A. Soares; Ismael L. Borges; Rodrigo C. Alves; Daniel M. Assis; Glaucia D. Kommers; Antonio F.M. Dantas; Glauco J.N. Galiza (Journal of Comparative Pathology, 2025)

Assessing genetics, biophysical, and management factors related to soybean seed protein variation in Brazil - María Sol Zelaya Arce; Eduardo Lago Lago Tagliapietra; José Eduardo Minussi Winck; Alexandre Ferigolo Alves; Felipe Schmidt Dalla Porta; Tiago Broilo Facco; Nereu Augusto Streck; Mauricio Fornalski Soares; Gregori Da Encarnação Ferrão; Daniel Debona; Claudio Hideo Martins da Costa; Rodrigo Merighi Bega; et al. (European Journal of Agronomy, 2025)

Correction: Restoration through trenches does not demand organic fertilization and sawdust coverage on plant establishment - Sabrina Santos Ribeiro; Walmer Bruno Rocha Martins; Julia Isabella de Matos Rodrigues; Victor Pereira de Oliveira; Denis Conrado da Cruz; Arystides Resende Silva; Gracialda Costa Ferreira; Rodrigo de Souza Barbosa; José do Carmo Alves Lopes; Anna Karyne Costa Rego; Gustavo Schwartz (Plant Ecology, 2025)

Ursolic acid derivatives improved clinical signs of experimental autoimmune encephalomyelitis by modulating central nervous system inflammation - Elaine Carlos Scherrer; Karla Antunes Ramos; Ydia Mariele Valadares; Igor Gabriel Machado Soares; Alessandra Paula Carli; Fernando Sá Silva; Jeferson Gomes Silva; Daniel Gomes Alvarenga; Alessa Sin Singer Brugiolo; Rodrigo Moreira Verly; Maiara Rodrigues Salvador; Angelo Marcio Leite Denadai; et al. (Metabolic Brain Disease, 2025)

Chemical Composition and Acaricidal and Insecticidal Activity of the Essential Oil of Tithonia diversifolia (Hemsl.) A. Gray (Asteraceae) - Roque Alves da Silva Júnior; Maressa de Carvalho Fragoso; Beatriz Astori Paraguassu; Rodrigues Agostinho Marcos; Rodrigo Scherer; Vanessa Moreira Osório; Hugo Bolsoni Zago; Tadeu Uggere de Andrade (Neotropical Entomology, 2025)

miR-512-3p as a Potential Biomarker of Poor Outcome in Pediatric Medulloblastoma - Carolina Alves Pereira Corrêa; Pablo Shimaoka Chagas; Mirella Baroni; Augusto Faria Andrade; Rosane Gomes de Paula Queiroz; Veridiana Kiill Suazo; Gustavo Alencastro Veiga Cruzeiro; Paola Fernanda Fedatto; David Santos Marco Antonio; Silvia Regina Brandalise; José Andres Yunes; Rodrigo Alexandre Panepucci; et al. (The Cerebellum, 2025)

Autosomal Recessive Ataxias in Northeast Brazil: A Regional Multicenter Case Series - Antonio Edvan Camelo-Filho; Rodrigo Fagundes da Rosa; Pedro Lucas Grangeiro Sá Barreto Lima; Gustavo Rodrigues Ferreira Gomes; Paula Camila Alves de Assis Pereira Matos; Deborah Moreira Rangel; Ellen Mourão Soares Lopes; Tamiris Carneiro Mariano; André Luiz Santos Pessoa; Paulo Ribeiro Nóbrega; Pedro Braga-Neto (The Cerebellum, 2025)

Assessment of potential ecological risk by metals in Ilha Grande Bay (Southeast Brazil) - Fabrício Leandro Damasceno; Maria Virgínia Alves Martins; Luiz Guilherme Costa Santos; João Graciano Mendonça Filho; Johann Hohenegger; Graziele Arantes Reis; Rodrigo dos Santos Diaz; Renata Cardia Rebouças; Thaise M. Senez-Mello; Sheila Arruda; Caroline Adolphsson do Nascimento; Murilo Barros Saibro; et al. (Marine Pollution Bulletin, 2025)

Toxicity of PAHs-enriched sediments on meiobenthic communities under ocean warming and CO2-driven acidification scenarios - Marcella Christina Soares Portugal; Giam Luca Altafim; Simone Brito de Jesus; Aline Vecchio Alves; Lino Angel Valcárcel Rojas; Eliete Zanardi-Lamardo; Italo Braga Castro; Fabiane Gallucci; Rodrigo Brasil Choueri (Marine Pollution Bulletin, 2025)

Behavioral and physiological effects of difenoconazole on stingless bees: A multi-species analysis - Renan dos Santos Araújo; Lorena Lisbetd Botina; Thaís Andrade Viana; Mateus Lordelo Vidigal; Beatriz Cristina da Silva Alves; Rodrigo Cupertino Bernardes; Gustavo Ferreira Martins (Science of The Total Environment, 2025)

Biometric and carcass analysis of lambs fed with forage palm silage and cottonseed cake - Iara Tamires Rodrigues Cavalcante; Wandrick Hauss de Sousa; Paulo Sérgio de Azevedo; Neila Lidiany Ribeiro; Rodrigo Couto Santos; Felipe Queiroga Cartaxo; João Paulo de Farias Ramos; Marcílio Fontes Cézar; Danillo Marte Pereira; Edson Mauro Santos; Juliana Silva de Oliveira; Marcos Vinícius da Silva; et al. (Small Ruminant Research, 2025)

Castration procedures and feed management in the finishing phase affect the performance, carcass traits, and meat quality of grazing steers - Jaqueline Rodrigues Ferreira Cara; Thiago Luis Alves Campos de Araújo; Andrei Pereira Néves; Karla Izidio Latta; Marília Williani Filgueira Pereira; Gilberto Romeiro de Oliveira Menezes; Gelson Luís Dias Feijó; Marina de Nadai Bonin Gomes; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2025)

Modulation of Eimeria spp. parasite load on productivity parameters in lambs fed with babassu byproduct - Sara Silva Reis; Henrique Nunes Parente; Anderson de Moura Zanine; Gisele Thamires Araújo da Silveira; Edegleicia Alves de Sousa; Arlan Araújo Rodrigues; Thalia Caldas da Silva; José Gracione do Nascimento Souza Filho; Janaina Marques do Nascimento; Thiago Vinicius Costa Nascimento; Michelle de Oliveira Maia Parente; Carlos Rodrigo Hermosilla; et al. (Tropical Animal Health and Production, 2025)

Suspect screening and quantitative analysis of 165 contaminants of emerging concern in water, sediments, and biota using LC-MS/MS: Ecotoxicological and human health risk assessment - Alice Cristina da Silva; Luan Valdemiro Alves de Oliveira; Luan Amaral Alexandre; Mateus Rocha Ribas; Juliana Lemos Dal Pizzol; Gustavo Rocha; Jussara Kasuko Palmeiro; Maurício Perin; Rodrigo Hoff; Silvani Verruck (Science of The Total Environment, 2025)

Mapping soil thickness using a mechanistic model and machine learning approaches - Nícolas Augusto Rosin; Danilo César de Mello; Benito R. Bonfatti; Alfred E. Hartemink; Tiago O. Ferreira; Nelida E.Q. Silvero; Raul Roberto Poppiel; Wanderson de S. Mendes; Gustavo Vieira Veloso; Márcio Rocha Francelino; Marcelo Rodrigo Alves; Renan Falcioni; et al. (CATENA, 2025)

Isolation, identification, and bioprospection of endophytic bacteria from medicinal plant Mikania glomerata (Spreng.) and the consortium of Pseudomonas as plant growth promoters - Bianca Rosini; Aline Maria Bulla; Julio Cesar Polonio; Andressa Domingos Polli; Angela Aparecida da Silva; Rodrigo Pawloski Schoffen; Verci Alves de Oliveira-Junior; Shalene da Silva Santos; Halison Correia Golias; João Lúcio Azevedo; João Alencar Pamphile (Biocatalysis and Agricultural Biotechnology, 2025)

Anorexigenic and anti-inflammatory signaling pathways of semaglutide via the microbiota–gut––brain axis in obese mice - Rodrigo Soares da Silva; Igor Henrique Rodrigues de Paiva; Ingrid Prata Mendonça; José Roberto Botelho de Souza; Norma Lucena-Silva; Christina Alves Peixoto (Inflammopharmacology, 2025)

qPCR as a Tool for the Diagnosis of Visceral and Cutaneous Leishmaniasis: A Systematic Review and Meta-Analysis - José Bryan Rihs; Mariana Teixeira Vilela; Janete Soares Coelho dos Santos; Job Alves de Souza Filho; Sérgio Caldas; Rodrigo Souza Leite; Marcos Paulo Gomes Mol (Acta Parasitologica, 2025)

SNP-based analysis reveals high genetic structure and diversity in umbu tree (Spondias tuberosa Arruda), a native and endemic species of the Caatinga biome - Wellington Ferreira do Nascimento; Flaviane Malaquias Costa; Alessandro Alves-Pereira; Carlos Eduardo de Araújo Batista; Igor Araújo Santos de Carvalho; Caroline Bertocco Garcia; Allison Vieira da Silva; Edson Ferreira da Silva; Márcia Maria de Souza Gondim Dias; Fábio Rodrigo Araújo Pereira; Maria Imaculada Zucchi; Elizabeth Ann Veasey (Genetic Resources and Crop Evolution, 2025)

Effects of dietary nucleotides on performance, proximate composition, health status, nitrogen stress resistance, and return on investment for Pacific white shrimp, Penaeus vannamei, raised in an intensive synbiotic system - Danielle Alves da Silva; Katharine Batista Santos de Souza; Gisely Karla de Almeida Costa; Suzianny Maria Bezerra Cabral da Silva; Fernando Leandro dos Santos; Rodrigo Antônio Ponce de Leon Ferreira de Carvalho; Giovanni Sampaio Gonçalves; João Fernando Albers Koch; Luis Otavio Brito (Aquaculture International, 2025)

First record of captive breeding of the ornamental fish L333, King Tiger Pleco, Hypancistrus sp. (Siluriformes – Loricariidae) of the Amazon River basin - Ryuller Gama Abreu Reis; Higo Andrade Abe; Pablo Costa Jastes Alves; Renata Silva de Oliveira; Ivana Kerly da Silva Viana; Rodrigo Takata; Rossineide Martins da Rocha (Aquaculture International, 2025)

CNT@NiFe2O4 nanocomposite for phenobarbital removal: adsorption study and characterization - Claudir Gabriel Kaufmann Junior; Rubia Young Sun Zampiva; Annelise koop Alves; Rafael Tronco; Marco Rossi; Carlos Perez Bergman; Leonardo Vidal Zancanaro; Sergio Roberto Mortari; Cristiano Rodrigo Bohn Rhoden (Environmental Science and Pollution Research, 2024)

Effects of metals in sediment under acidification and temperature rise scenarios on reproduction of the copepod Nitokra sp. - Aline Vecchio Alves; Rafael Keiji Kureki; Tailisi Hoppe Trevizani; Rubens Cesar Lopes Figueira; Rodrigo Brasil Choueri (Marine Pollution Bulletin, 2024)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a pasture-based feeding system submitted to ovulation induction strategies prior to a timed-artificial insemination protocol - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Patrícia R. Cavalcanti; Mirela Balistrieri; Gustavo V. Barros; Edgar Nagle; Roberto Sartori (Theriogenology, 2024)

Microbiota diversity of three Brazilian native fishes during ice and frozen storage - Rafaela C. Baptista; Ilario Ferrocino; Matheus Pavani; Tatiane M. Guerreiro; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Rodrigo R. Catharino; Elenilson G. Alves Filho; Sueli Rodrigues; Edy S. de Brito; Magdevis Y.R. Caturla; et al. (Food Microbiology, 2024)

Mesoproterozoic depleted spinel peridotites metasomatized by high-K hydrous melt in the Patagonian back-arc - Aline Alves dos Santos; Tiago Jalowitzki; Fernanda Gervasoni; Maurizio Mazzucchelli; Tommaso Giovanardi; Manuel Enrique Schilling; Maria Isabel Varas-Reus; Yuji Orihashi; Rodrigo Freitas Rodrigues; Richard Walter Carlson; Georgina Marianela Rubiano Lorenzoni; Daiji Hirata; et al. (Chemical Geology, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

Ascophyllum nodosum-derived biostimulant promotes physiological conditioning to increase soybean yield in a semiarid climate - Jeane Ferreira de Jesus; Amanda Soares Santos; Renato Oliveira de Sousa; Bruno Sousa Figueiredo da Fonseca; Wesley Santos Ferreira; Rodrigo Fonseca da Silva; Stelamaris de Oliveira Paula-Marinho; Priscila Alves Barroso; Milena Rodrigues Luz; Francisco de Alcântara Neto; José Hélio Costa; Rafael de Souza Miranda (Journal of Applied Phycology, 2024)

Predicting health impacts of wildfire smoke in Amazonas basin, Brazil - Yara de Souza Tadano; Sanja Potgieter-Vermaak; Hugo Valadares Siqueira; Judith J. Hoelzemann; Ediclê S.F. Duarte; Thiago Antonini Alves; Fabio Valebona; Iuri Lenzi; Ana Flavia L. Godoi; Cybelli Barbosa; Igor O. Ribeiro; Rodrigo A.F. de Souza; et al. (Chemosphere, 2024)

Landscape and insecticide use affecting the Leucoptera coffeella infestation and the natural parasitism spatiotemporal distribution in brazilian coffee agroecosystems - Mateus Pereira dos Santos; Benício de Melo Santos Neto; Lilian Rocha Araújo; Ana Carolina Plácido Cardoso; Beatriz Sousa Coelho; Suzany Aguiar Leite; Aldenise Alves Moreira; Daniell Rodrigo Rodrigues Fernandes; Geraldo Andrade Carvalho; Maria Aparecida Castellani (Crop Protection, 2024)

Water level regime variation is a crucial driver for taxonomic, functional, and phylogenetic diversity in seasonally flooded tropical forests - Fernanda Moreira Gianasi; Vinícius de Andrade Maia; Aline Meyer Oliveira; Patrícia Vieira Pompeu; Cléber Rodrigo de Souza; Camila Laís Farrapo; André Maciel da Silva-Sene; Fernanda de Oliveira; Thiago Magalhães Meireles; Ana Lívia de Carvalho Rodrigues; Denise Moura Madeira; Felipe Carvalho Araújo; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Supplementation of high doses of vitamin D during the gestational period do not cause reproductive, teratogenic and genotoxic damage in mice - Silvia Cordeiro das Neves; Sarah Alves Auharek; Roberto da Silva Gomes; Marcelo Luiz Brandão Vilela; Valter Aragão do Nascimento; Henrique Rodrigues Scherer Coelho; Karuppusamy Arunachalam; Andréia Conceição Milan Brochado Antoniolli-Silva; Rodrigo Juliano Oliveira (Food and Chemical Toxicology, 2024)

Corrigendum to Effects of blood metal(loid) concentrations on genomic damages in sharks [Environ. Pollut. 359 (2024) 124569] - Camila Brasilino Botêlho de Araújo; Sibele Alves de Mendonça; Danielle de Lima Viana; Mariana da Fontoura Martins; Patrícia Gomes Costa; Adalto Bianchini; Paulo Guilherme Vasconcelos de Oliveira; Rodrigo Augusto Torres; Fábio Hissa Vieira Hazin; Mônica Lúcia Adam (Environmental Pollution, 2024)

Genetic loci associated with sorghum drought tolerance in multiple environments and their sensitivity to environmental covariables - Karine da Costa Bernardino; José Henrique Soler Guilhen; Cícero Beserra de Menezes; Flavio Dessaune Tardin; Robert Eugene Schaffert; Edson Alves Bastos; Milton José Cardoso; Rodrigo Gazaffi; João Ricardo Bachega Feijó Rosa; Antônio Augusto Franco Garcia; Claudia Teixeira Guimarães; Leon Kochian; et al. (Theoretical and Applied Genetics, 2024)

High removal of volatile organic compounds on hierarchical carbons prepared from agro-industrial waste of banana fruit production for air decontamination - José Luiz Cunha Cordeiro; Rodrigo Santos Gonzaga Menezes; Matheus Chaves Moreira da Silva; Mauricio Brandão dos Santos; Fernanda Teixeira Cruz; Heloysa Martins Carvalho Andrade; Artur José Santos Mascarenhas; Raildo Alves Fiuza-Junior (Environmental Science and Pollution Research, 2024)

A New Species of Nealiolus Mason, 1974 (Hymenoptera: Braconidae) from Traditional Cocoa Agroforestry and Brazilian Atlantic Rainforest - Antonielson Bezerra Silva; José Victor Alves Ferreira; Maíra Benchimol; Eduardo Mitio Shimbori; Daniell Rodrigo Rodrigues Fernandes (Neotropical Entomology, 2024)

PCBs contamination in water and Mytilus edulis along the north Portuguese Atlantic Ocean coastline and analysis of potential carcinogenic risk to human health - Ana Margarida Esteves; Rodrigo Alves; Eduardo Rocha; Maria João Rocha (Marine Pollution Bulletin, 2024)

“Cocaine Shark”: First report on cocaine and benzoylecgonine detection in sharks - Gabriel de Farias Araujo; Luan Valdemiro Alves de Oliveira; Rodrigo Barcellos Hoff; Natascha Wosnick; Marcelo Vianna; Silvani Verruck; Rachel Ann Hauser-Davis; Enrico Mendes Saggioro (Science of The Total Environment, 2024)

Effects of blood metal(loid) concentrations on genomic damages in sharks - Camila Brasilino Botêlho de Araújo; Sibele Alves de Mendonça; Danielle de Lima Viana; Mariana da Fontoura Martins; Patrícia Gomes Costa; Adalto Bianchini; Paulo Guilherme Vasconcelos de Oliveira; Rodrigo Augusto Torres; Fábio Hissa Vieira Hazin; Mônica Lúcia Adam (Environmental Pollution, 2024)

A Cluster of Diutina catenulata Funguria in Patients with Coronavirus Disease 2019 (COVID-19) Hospitalized in a Tertiary Reference Hospital from Rio de Janeiro, Brazil - Rodrigo Almeida-Paes; Marcus de Melo Teixeira; Fernanda Alves de Oliveira; Marcos de Abreu Almeida; Fernando Almeida-Silva; Kim Mattos Geraldo; Estevão Portela Nunes; Bridget M. Baker; Jason E. Stajich; Beatriz Grinsztejn; Valdilea Gonçalves Veloso; Andrea d’Avila Freitas; et al. (Current Microbiology, 2024)

Subacute tributyltin exposure alters the development and morphology of mammary glands in association with CYP19A1 expression in female rats - Natalia P. Silva; Charles S. da Costa; Kayke L. Barbosa; Cidália de F. Januario; Leticia N. Gama-de-Souza; Cinthia Breves; Rodrigo S. Fortunato; Leandro Miranda-Alves; Miriane de Oliveira; Celia R. Nogueira; Jones B. Graceli (Reproductive Toxicology, 2024)

The mlpt smORF gene is essential for digestive physiology and molting during nymphal stages in the kissing bug Rhodnius prolixus - Carina Azevedo Oliveira Silva; Sandy da Silveira Alves; Bruno da Costa Rodrigues; Jonatha Anderson Fraga Egidio; Lupis Ribeiro; Carlos Logullo; Flavia Borges Mury; Daniele das Graças Santos; Taynan Portal; Cintia Monteiro-de-Barros; José Roberto da Silva; José Luciano Nepomuceno-Silva; et al. (Insect Biochemistry and Molecular Biology, 2024)

Chemical constraints are the major limiting factor of root deepening in southern Brazil soils - Rodrigo Pivoto Mulazzani; Daniel Boeno; Bruna San Martin Rolim Ribeiro; Alexandre Ferigolo Alves; Alencar Junior Zanon; Paulo Ivonir Gubiani (Geoderma Regional, 2024)

Contamination risk by heavy metals and enzymatic stoichiometry in agricultural soils under intense use of pesticides - Thais da Silva Martins; Kaio Gráculo Vieira Garcia; Yuri Jacques Agra Bezerra da Silva; Mateus Guimarães da Silva; Sheilla Silva e Serpa; Rodrigo Alves Bezerra; Crisanto Dias Teixeira Filho; Rivelino Martins Cavalcante; Cácio Luiz Boechat; Arthur Prudêncio de Araujo Pereira; Maria Eugenia Ortiz Escobar (Environmental Monitoring and Assessment, 2024)

Use of crude glycerin in dairy goat feeding and its effects on milk and cheese performance and quality - Rodrigo Barbosa de Andrade; Kelly Cristina dos Santos; Érica Carla Lopes da Silva; Edneide Rodrigues da Silva; Michel do Vale Maciel; João Paulo Ismério dos Santos Monnerat; Dorgival Morais de Lima Júnior; Neila Mello dos Santos Cortez; Maria Gabriela da Conceição; Susana Paula Almeida Alves; Rui José Branquinho de Bessa; Francisco Fernando Ramos de Carvalho (Animal Feed Science and Technology, 2024)

Geotechnologies on the phosphorus stocks determination in tropical soils: General impacts on society - Jorge Tadeu Fim Rosas; José A.M. Demattê; Nícolas Augusto Rosin; Bruno dos Anjos Bartsch; Raul Roberto Poppiel; Heidy Soledad Rodriguez-Albarracin; Jean Jesus Macedo Novais; Paulo Sergio Pavinato; Yuxin Ma; Danilo César de Mello; Marcio Rocha Francelino; Marcelo Rodrigo Alves (Science of The Total Environment, 2024)

Restoration through trenches does not demand organic fertilization and sawdust coverage on plant establishment - Sabrina Santos Ribeiro; Walmer Bruno Rocha Martins; Julia Isabella de Matos Rodrigues; Victor Pereira de Oliveira; Denis Conrado da Cruz; Arystides Resende Silva; Gracialda Costa Ferreira; Rodrigo de Souza Barbosa; José do Carmo Alves Lopes; Anna Karyne Costa Rego; Gustavo Schwartz (Plant Ecology, 2024)

Poleward catch displacement of blackfin tuna Thunnus atlanticus in the southwestern Atlantic Ocean: Possible effect of increasing water temperatures - Luís Gustavo Cardoso; Rodrigo Sant'Ana; Marcio de Araújo Freire; Stefan Cruz Weigert; Marina Poubel; Natalia Alves Bezerra; Lucas dos Santos Rodrigues (Fisheries Management and Ecology, 2024)
Blackfin tuna Thunnus atlanticus often inhabits warm waters of the western Atlantic Ocean from 40°N (Cape Cod, USA) to 22°S (Rio de Janeiro, Brazil). We recorded the first catches of the species in southern Brazil (34°S) and described its new distribution and fishing grounds. Since 2007, annual catches per trip and frequency of blackfin tuna landings increased for three oceanic fishing fleets in Southern Brazil. The spatial distribution of higher catches and the center of gravity of spatial fishing records moved poleward. Sea surface temperature anomalies for the region warmed from 1960 to 2019, and anomalies were primarily positive after 2000. Evidence suggests that the distribution of blackfin tuna moved poleward by six degrees of latitude (~660 km). The causes of this distribution extension were unclear, but ocean warming was the most likely driver.

Semaglutide Attenuates Anxious and Depressive-Like Behaviors and Reverses the Cognitive Impairment in a Type 2 Diabetes Mellitus Mouse Model Via the Microbiota-Gut-Brain Axis - Igor Henrique Rodrigues de Paiva; Rodrigo Soares da Silva; Ingrid Prata Mendonça; José Roberto Botelho de Souza; Christina Alves Peixoto (Journal of Neuroimmune Pharmacology, 2024)

Timed-artificial insemination protocols for Bos indicus beef heifers: Evaluation of protocol length and variations in prostaglandin F2α treatments - Rodrigo L.O.R. Alves; Lucas O.e Silva; Mateus A.da Silva; Carlos E.C. Consentini; José R.S. Gonçalves; Leonardo de F. e Melo; Marcelo B. Rodrigues; Roberto Sartori (Theriogenology, 2024)

Fermentation of coffee fruit with sequential inoculation of Lactiplantibacillus plantarum and Saccharomyces cerevisiae: effect on sensory attributes and chemical composition of the beans - Flávio Meira Borém; Mariane Helena Sances Rabelo; Ana Paula de Carvalho Alves; Cláudia Mendes Santos; Rodrigo Soares Pieroni; Makoto Nakajima; Ryosuke Sugino (Food Chemistry, 2024)

Conversion of microalgae into renewable hydrocarbons through catalytic pyrolysis: A bibliometric analysis - Joemil Oliveira de Deus Junior; José Luiz Francisco Alves; Vitor Rodrigo de Melo e Melo; Ângelo Anderson Silva de Oliveira; Karine Fonseca Soares de Oliveira; Dulce Maria de Araújo Melo; Renata Martins Braga (Algal Research, 2024)

Unraveling DEHP influence on hemoglobin S polymerization in sickle cell disease: Ex vivo, in vitro and in silico analysis - Rodrigo Abreu Camacho; Aghata Vitoria Machado; Fernanda de Oliveira Mendonça; Lyzes Rosa Teixeira-Alves; Camila Cristina Guimarães-Nobre; Evelyn Mendonça-Reis; Priscila Ferreira da Silva; Thyago R. Cardim-Pires; Leandro Miranda-Alves; Clemilson Berto-Junior (Toxicology in Vitro, 2024)

How temperature modulates the expression of pathogenesis-related molecules of the cross-kingdom pathogen Lasiodiplodia hormozganensis - Carina Félix; Rodrigo Meneses; Micael F.M. Gonçalves; Ana S. Duarte; Jesus V. Jorrín-Novo; Yves van de Peer; Dieter Deforce; Filip Van Nieuwerburgh; Artur Alves; Ana C. Esteves (Science of The Total Environment, 2024)

Fermentation of coffee fruit with sequential inoculation of Lactiplantibacillus plantarum and Saccharomyces cerevisiae: Effects on volatile composition and sensory characteristics - Mariane Helena Sances Rabelo; Flávio Meira Borém; Ana Paula de Carvalho Alves; Rodrigo Soares Pieroni; Claudia Mendes Santos; Makoto Nakajima; Ryosuke Sugino (Food Chemistry, 2024)

Stemphylium lycopersici immobilized in polyurethane (PU) treated in pressurized fluid CO2 as biocatalyst for ω-transamination reactions - Maria Sandra Ramos Queiroz; Nádia Ligianara Dewes Nyari; Carolina Lixa Victor Neves; Anderson de Sá Pinheiro; Marcelo Luis Mignoni; Rogério Marcos Dallago; Rodrigo Otávio Mendonça Alves de Souza; Denise Oliveira Guimarães; Ivana Correa Ramos Leal (Biocatalysis and Agricultural Biotechnology, 2024)

Multispecies and multibiomarker assessment of fish health from Iguaçu River reservoir, Southern Brazil - Dámaso Angel Rubio-Vargas; Tobias Pereira de Morais; Marco Antonio Ferreira Randi; Francisco Filipak Neto; Cláudia Feijó Ortolani-Machado; César de Castro Martins; Andrea Pinto Oliveira; Mariana Gallucci Nazário; Fernando Cesar Alves da Silva Ferreira; Iracema Opuskevitch; Dieter Penner; Juan Esquivel-Muelbert; et al. (Environmental Monitoring and Assessment, 2024)

New thymol-derived triazole exhibits promising activity against Trichophyton rubrum - Thiago Antonio de Sousa Cutrim; Mariana Alves Eloy; Fernando Fontes Barcelos; Leandra Martins Meireles; Lara Chaves de Freitas Ferreira; Tatiana Alves Reis; Sarah Santos Gonçalves; Valdemar Lacerda; Marcio Fronza; Pedro Alves Bezerra Morais; Rodrigo Scherer (Brazilian Journal of Microbiology, 2024)

Fishing and recording dead fish by citizen scientists contribute valuable data on south American ray-finned fish diversity - Lucas Rodriguez Forti; José Luís Costa Novaes; Milena Wachlevski; Rodrigo Silva da Costa; Jandson Lucas Camelo da Silva; Juan Lima; Adriana Maria Alves; Lorena B. Thaíza Fernandes; Judit K. Szabo (Biodiversity and Conservation, 2024)

Agroforestry can improve soil fertility and aggregate-associated carbon in highland soils in the Brazilian northeast - Rodrigo Santana Macedo; Letícia Moro; Cristiano dos Santos Sousa; Kalline de Almeida Alves Carneiro; Milton César Costa Campos; Alexandre Pereira de Bakker; Raphael Moreira Beirigo (Agroforestry Systems, 2024)

A comparative proteomic analysis between common cashew tree ( Anacardium occidentale L.) and early dwarf faga 11 ( Anacardium occidentale var. nanum ) seeds reveals exclusively expressed allergenic proteins - Vitória Virginia Magalhães Soares; Carlos Franciney Moreira Vasconcelos; João Garcia Alves Filho; Frederico Bruno Mendes Batista Moreno; Ana Cristina de Oliveira Monteiro Moreira; Rodrigo Maranguape Silva da Cunha (Plant Biosystems, 2024)

Search for new green natural solid phases for sample preparation for PAHs determination in seafood samples followed by LC and GC–MS/MS analysis - Luana Souza Futigami; Rodrigo Barcellos Hoff; Carolina Turnes Pasini Deolindo; Cristian Rafael Kleemann; Luan Valdomiro Alves de Oliveira; Alicia de Francisco de Casas; Vivian Maria Burin (Food Research International, 2024)

Spatializing soil elemental concentration as measured by X-ray fluorescence analysis using remote sensing data - Nícolas Augusto Rosin; José A.M. Demattê; Hudson Wallace Pereira de Carvalho; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Jean Jesus Novais; Ricardo S.D. Dalmolin; Marcelo Rodrigo Alves; Renan Falcioni; Nikolaos Tziolas; Sina Mallah; Danilo César de Mello; et al. (CATENA, 2024)

Organosulfur and Organoselenium Functionalized Benzimidazo[1,2-a]quinolines: From Experimental and Theoretical Photophysics to All-Solution-Processed OLEDs - Rodrigo Borges da Silva; Felipe Lange Coelho; Henrique de Castro Silva Junior; José Carlos Germino; Teresa Dib Zambon Atvars; Fabiano Severo Rodembusch; Luís Gustavo Teixeira Alves Duarte; Paulo Henrique Schneider (Journal of Fluorescence, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Statistical methods for genetic evaluation and selection of parents and hybrids of grain sorghum - Leonardo Volpato; Saulo Fabrício da Silva Chaves; Rodrigo Silva Alves; João Romero do Amaral Santos de Carvalho Rocha; Regimar Garcia dos Santos; Larissa Pereira Ribeiro Teodoro; Flávio Dessaune Tardin; Aisy Botega Baldoni; Cicero Beserra de Menezes; Marcos Deon Vilela de Resende; Paulo Eduardo Teodoro (South African Journal of Botany, 2024)

Carcass characteristics and meat quality of cull cows from different genetic groups - Karla Izidio Latta; Luís Carlos Vinhas Ítavo; Rodrigo da Costa Gomes; Marina de Nadai Bonin Gomes; Jaqueline Rodrigues Ferreira; Andrei Pereira Neves; Thiago Alves Campos de Araujo; Gelson Luís Dias Feijó; Gilberto Romeiro de Oliveira Menezes (Livestock Science, 2024)

Antiviral potential of bio-oil from Citrus sinensis waste wood as a therapeutic approach against COVID-19 - João Gilberto Meza Ucella-Filho; Nicolly Soares Ferreira; Gabriela Fontes Mayrinck Cupertino; Natália Assis Guedes; Heberth de Paula; Rodrigo Rezende Kitagawa; Alina Mariana Balu; Rafael Luque; Mariana Drummond Costa Ignacchiti; Luciana Alves Parreira; Juliana Alves Resende; Ananias Francisco Dias Junior (Journal of Cleaner Production, 2024)

Prebiotics modulate the microbiota–gut–brain axis and ameliorate anxiety and depression-like behavior in HFD-fed mice - Igor Henrique Rodrigues de Paiva; Laís Macedo Maciel; Rodrigo Soares da Silva; Ingrid Prata Mendonça; José Roberto Botelho de Souza; Christina Alves Peixoto (Food Research International, 2024)

Functional and structural attributes of Brazilian tropical and subtropical forests and savannas - Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Renata Dias Françoso; Vinícius Andrade Maia; José Roberto Rodrigues Pinto; Pedro Higuchi; Ana Carolina Silva; Jamir Afonso do Prado Júnior; Camila Laís Farrapo; Eddie Lenza; Henrique Mews; Helena L. Lemos Rocha; et al. (Forest Ecology and Management, 2024)

Dietary effect of multi-strain prebiotics and probiotics on growth, hemato-biochemical parameters, intestinal histomorphometry, and resistance to hypoxia in juvenile tambaqui (Colossoma macropomum) - Rafael José Furtado Souza; Edilson Rodrigues Matos; Aldry Lorran da Silva Souza; Paola Fabiana Fazzi-Gomes; Nuno Filipe Alves Correia de Melo; Marco Shizuo Owatari; Glauber David Almeida Palheta; Rodrigo Takata; Fabio Carneiro Sterzelecki (Veterinary Research Communications, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

In vitro culture of Rio Grande cherry (Eugenia involucrata DC.) - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Rodrigo Rocha Latado; Sônia Maria De Stefano Piedade; Francisco de Assis Alves Mourão Filho (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

PAH residues and toxicity levels two years after an extensive oil spill on the northeast Brazilian coast - Rodrigo Brasil Choueri; Denis Moledo de Souza Abessa; Maysa Ueda de Carvalho; Bianca Pazini; Eliete Zanardi-Lamardo; Lino Angel Valcárcel Rojas; Paulo Sérgio Martins de Carvalho; Nycolle Virgínia Maux de Andrade; Lília Pereira de Souza Santos; Mariana Aliceda Ferraz; Aline Vecchio Alves; Ítalo Braga Castro (Marine Pollution Bulletin, 2024)

Mining-free territories and decolonial theory: Evaluating the synergies in the Brazilian context - Rodrigo Machado Vilani; Bruno Milanez; Márcia Barbosa Martins; Maria Amália Silva Alves de Oliveira; Carlos José Saldanha Machado; Marília Luisa de Oliveira (The Extractive Industries and Society, 2024)

Association of rainfall pattern with the disappearance of mineral mixtures fed cattle managed on tropical pastures - Zey Welington Gomes de Souza; Manoel Gustavo Paranhos da Silva; Andrei Pereira Neves; Thiago Luís Alves Campos de Araújo; Nickson Milton Correa Siqueira; Wallyson Almeida Amaral; Denise Baptaglin Montagner; Luís Carlos Vinhas Ítavo; Valter Bumbieris Júnior; Bruno Marson; Márcio de Nadai Bonin; Rodrigo da Costa Gomes (Tropical Animal Health and Production, 2024)

Environmental vulnerability index in Dipteryx alata: influence of abiotic stresses on central processes of plant physiology and metabolism - Leticia Ferreira Sousa; Paulo Eduardo Menezes-Silva; Priscila Ferreira Batista; Ana Paula Silva Alves; Maria Clara de Andrade PereiraSilva; Sabrina Emanuella da Silva Almeida; Rauander Douglas Ferreira Barros Alves; Lucas Loram Lourenço; Layara Alexandre Bessa; Adinan Alves da Silva; Alan Carlos Costa; Anderson Rodrigo da Silva; et al. (Acta Physiologiae Plantarum, 2024)

Low doses of malathion impair ovarian, uterine, and follicular integrity by altering oxidative profile and gene expression of rats exposed during the peripubertal period - Rafaela Pires Erthal-Michelato; Giovanna Fachetti Frigoli; Ariana Musa de Aquino; Ana Paula Franco Punhagui-Umbelino; Wellerson Rodrigo Scarano; Glaura Scantamburlo Alves Fernandes (Environmental Science and Pollution Research, 2024)

Pollutant bioaccumulation in sentinel fish chronically exposed in Iguaçu river reservoirs (Southern Brazil) and human health risk of fish consumption - Dámaso Angel Rubio-Vargas; Tobias Pereira de Morais; Marco Antônio Ferreira Randi; Francisco Filipak Neto; César de Castro Martins; Andrea Pinto Oliveira; Mariana Gallucci Nazário; Fernando Cesar Alves da Silva Ferreira; Iracema Opuskevitch; Dieter Penner; Juan Esquivel-Muelbert; Maritana Mela Prodocimo; et al. (Chemosphere, 2024)

The role of habitat heterogeneity and timescales on the recovery of reef epifaunal communities affected by a massive oil spill in the tropics - José S. Rosa Filho; Rodrigo V.A. Alves; Ingrid T. Santos; Matheus A. Oliveira; Flávia L. Frédou; Nykon Craveiro (Marine Pollution Bulletin, 2024)

Emergent properties of free-living nematode assemblages exposed to multiple stresses - Nilvea Ramalho Oliveira; Giam Luca Altafim; Aline Vecchio Alves; Rodrigo Brasil Choueri; Juliano Zanette; Rubens Cesar Lopes Figueira; Fabiane Gallucci (Science of The Total Environment, 2024)

Exploring the potential of tannin-rich tree bark extracts in combating foodborne diseases and gastric cancer - João Gilberto Meza Ucella-Filho; Mario Sérgio Lorenço; Bruna Rafaella Ferreira da Silva; Vanuzia Rodrigues Fernandes Ferreira; Jessica Raquel Borges Monteiro; Nicolly Soares Ferreira; Maria das Graças Cardoso; Rodrigo Rezende Kitagawa; Juliana Alves Resende; Ananias Francisco Dias Junior; Roberta Hilsdorf Piccoli; Fábio Akira Mori (Food Bioscience, 2024)

Somatic embryogenesis in Euterpe edulis Martius is improved by wounding, explant orientation, and suspension culture - Tamyris de Mello; Tatiane Dulcineia Silva; Tadeu Ériton Caliman Zanardo; Francine Alves Nogueira de Almeida; Luciano Bestete Oliveira; Clovis Eduardo Nunes Hegedus; Breno Benvindo dos Anjos; Edilson Romais Schmildt; Adésio Ferreira; Márcia Flores da Silva Ferreira; José Carlos Lopes; Glória Maria de Farias Viégas Aquije; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Growth, survival, and myogenic gene expression in the post-larvae of Colossoma macropomum provisioned with Artemia nauplii - Debora Sayumi Doami Melo; André Luiz Alves de Sá; Sávio Lucas de Matos Guerreiro; Joane Natividade; Paola Fabiana Fazzi Gomes; Rodrigo Takata; Ednaldo da Silva Filho; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; Fabio Carneiro Sterzelecki; Igor Hamoy (Fish Physiology and Biochemistry, 2024)

Influence of GnRH analog and dose on LH release and ovulatory response in Bos indicus heifers and cows on day seven of the estrous cycle - Lucas O. e Silva; Jessica C.L. Motta; Abraham L. Oliva; Guilherme Madureira; Rodrigo L.O.R. Alves; Natália P. Folchini; Mateus A. da Silva; Taynara J.B. da Silva; Carlos E.C. Consentini; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2024)

The end of an entire biome? World's largest wetland, the Pantanal, is menaced by the Hidrovia project which is uncertain to sustainably support large-scale navigation - Karl M. Wantzen; Mario Luis Assine; Ieda Maria Bortolotto; Debora Fernandes Calheiros; Zilca Campos; Agostinho Carlos Catella; Rafael Morais Chiaravalotti; Walter Collischonn; Eduardo Guimarães Couto; Catia Nunes da Cunha; Geraldo Alves Damasceno-Junior; Carolina Joana da Silva; et al. (Science of The Total Environment, 2024)

Coffee yield prediction using high-resolution satellite imagery and crop nutritional status in Southeast Brazil - Marco Antonio Zanella; Rodrigo Nogueira Martins; Fábio Moreira da Silva; Luis Carlos Cirilo Carvalho; Marcelo de Carvalho Alves; Jorge Tadeu Fim Rosas (Remote Sensing Applications: Society and Environment, 2024)

The terroir of Brazilian Coffea canephora: Characterization of the chemical composition - Bárbara Zani Agnoletti; Lucas Louzada Pereira; Enrique Anastácio Alves; Rodrigo Barros Rocha; Danieli Gracieri Debona; Marcos Valério Vieira Lyrio; Taís Rizzo Moreira; Eustáquio Vinicius Ribeiro de Castro; Emanuele Catarina da S. Oliveira; Paulo Roberto Filgueiras (Food Research International, 2024)

What future for marine renewable energy in Portugal and Spain up to 2030? Forecasting plausible scenarios using general morphological analysis and clustering techniques - Mário Vieira; Ana Macedo; António Alvarenga; Marcos Lafoz; Isabel Villalba; Marcos Blanco; Rodrigo Rojas; Alejandro Romero-Filgueira; Adriana García-Mendoza; Miguel Santos-Herran; Marco Alves (Energy Policy, 2024)

Strategies of virginiamycin supplementation in the postweaning phase on growth performance and carcass quality of beef cattle - Rodrigo da Costa Gomes; Gilberto Romeiro de Oliveira Menezes; Ricardo Favero; Ricardo Kazama; Georg Altrak; Ivone Yurika Mizubuti; Marina de Nadai Bonin Gomes; Gelson Luis Dias Feijó; Denise Baptaglin Montagner; Thiago Luís Alves Campos de Araújo; Dorgival Morais de Lima Júnior; Roberto Augusto de Almeida Torres Júnior; et al. (Tropical Animal Health and Production, 2024)

Environmental monitoring of SARS-CoV-2 in the metropolitan area of Porto Alegre, Rio Grande do Sul (RS), Brazil - Leticia Batista Dutra; Janaína Francieli Stein; Bruna Seixas da Rocha; Andresa Berger; Beatriz Andrade de Souza; Bruno Aschidamini Prandi; Arthur Tonietto Mangini; André Jarenkow; Aline Alves Scarpellini Campos; Fernando Mainardi Fan; Maria Cristina de Almeida Silva; Katia Helena Lipp-Nissinen; et al. (Environmental Science and Pollution Research, 2023)
Since starts the coronavirus disease 2019 (COVID-19) pandemic identified the presence of genomic fragments of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in various environmental matrices: domestic sewage, surface waters, and contaminated freshwater. Environmental monitoring of SARS-CoV-2 is a tool for evaluating trend curves over the months, compared to several clinical cases of the disease. The objective of this study was to monitor the SARS-CoV-2 in environmental samples collected in different sites in a metropolitan area of Porto Alegre, Southern Brazil. During 10 months from 2020 to 2021, 300 samples were collected weekly and biweekly from nine points located in 3 cities: one point from a wastewater treatment plant (WWTP) in São Leopoldo (fortnightly collection), two points in Dilúvio Stream in Porto Alegre (fortnightly collection), two points in Pampa and Luiz Rau Streams (weekly collection), and two points in public fountains (fortnightly collection) in Novo Hamburgo. After collection, samples were concentrated by ultracentrifugation, and viral nucleic acids were extracted using MagMax® Core Nucleic Acid Purifications kits and submitted to RT-qPCR, using E, N1, and N2 gene targets of SARS-CoV-2. Only 7% (3/41) samples from public fountains were positive, with a mean viral load (VL) of SARS-CoV-2 RNA of 5.02 × 10 1 gc/l (2.41~8.59 × 10 1 gc/l), while the streams had average VL of 7.43 × 10 5 gc/l (Pampa), 7.06 × 10 5 gc/l (Luiz Rau), 2.01 × 10 5 gc/l (Dilúvio), and 4.46 × 10 5 cg/l (WWTP). The results showed varying levels of viral presence in different sample types, with a demonstrated correlation between environmental viral load and clinical COVID-19 cases. These findings contribute to understanding virus persistence and transmission pathways in the environment. Continuous monitoring, especially in less developed regions, is crucial for early detection of vaccine resistance, new variants, and potential COVID-19 resurgence.

Do tides equally influence the reproductive cycle of two symbiotic estuarine shrimp? - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Magnetic heterostructures of NiFe2O4 and TiO2: Pechini synthesis, characterization and photocatalytic performance in arsenite oxidation - Giulia Caroline de Cristo Borges; Isadora Roberta Verdi; Michel Zampieri Fidelis; Henrique Emilio Zorel Junior; Giane Gonçalves Lenzi; Éder Carlos Ferreira de Souza; Odivaldo Cambraia Alves; Rodrigo Brackmann (Journal of Water Process Engineering, 2023)

Integrated planning of forest exploration infrastructures in an amazonian sustainable forest management area - Marcelo Otone Aguiar; Gilson Fernandes da Silva; Geraldo Regis Mauri; Adriano Ribeiro de Mendonça; Evandro Ferreira da Silva; Evandro Orfano Figueiredo; Jeferson Pereira Martins Silva; Valéria Alves da Silva; Rodrigo Freitas Silva; Gabriel Lessa Lavagnoli (Forest Ecology and Management, 2023)

The striatum drives the ergogenic effects of caffeine - Ana Cristina de Bem Alves; Ana Elisa Speck; Hémelin Resende Farias; Leo Meira Martins; Naiara Souza dos Santos; Gabriela Pannata; Ana Paula Tavares; Jade de Oliveira; Ângelo R. Tomé; Rodrigo A. Cunha; Aderbal S Aguiar (Purinergic Signalling, 2023)

Tree hydrological niche acclimation through ontogeny in a seasonal Amazon forest - Mauro Brum; Luciana F. Alves; Raimundo C. de Oliveira-Junior; Victor Hugo Pereira Moutinho; Natalia Restrepo-Coupe; Karoline Chaves; Deliane Penha; Neill Prohaska; Plínio Barbosa de Camargo; Grazielle Sales Teodoro; Sebastião Ribeiro Xavier Júnior; Scott C. Stark; et al. (Plant Ecology, 2023)

Stay here, but keep quiet: the effects of anthropogenic noise on Guiana dolphins (Sotalia guianensis) in southeastern Brazil - Israel Maciel; Teresa Belderrain; Maria Alice S. Alves; Rodrigo Tardin (Marine Biology, 2023)

Polyhexamethylene guanidine hydrochloride as promising active ingredient for oral antiseptic products to eliminate microorganisms threatening the health of endangered wild cats: a comparative study with chlorhexidine digluconate - Renata Alves de Barros; Marcela Aldrovani Rodrigues; Sérgio Ricardo Ambrósio; Rodrigo Cássio SolaVeneziani; Daniel Paulino Júnior; Renato Luis Tame Parreira; Maria Anita Lemos Vasconcelos Ambrósio; Thayná de Souza Silva; Lucas de Freitas Pereira; Messias Gonçalves Pessinato; Vinícius José da Silva Cardoso de Brito; César Henrique Branco; et al. (Brazilian Journal of Microbiology, 2023)

Antitumor and antibacterial activity of metabolites of endophytic Colletotrichum siamense isolated from coffee (Coffea arabica L. cv IAPAR-59) - Bruno César do Espírito Santo; João Arthur dos Santos Oliveira; Marcos Alessandro dos Santos Ribeiro; Rodrigo Pawloski Schoffen; Andressa Domingos Polli; Julio Cesar Polonio; Angela Aparecida da Silva; Benício Alves de Abreu Filho; Michele Cristina Heck; Eduardo César Meurer; Paola Pereira Constantin; Marcos Pileggi; et al. (Brazilian Journal of Microbiology, 2023)

A new blue Astrangia coral (Scleractinia) from the Southwestern Atlantic - Saulo Serra; Elizabeth Gerardo Neves; Jessika Alves; Rodrigo Johnsson (Marine Biodiversity, 2023)

Locomotion behavior testing as a complementary tool in Collembola avoidance assays with neurotoxic insecticides - Felipe Ogliari Bandeira; Jéssica Karolayne Tina; Paulo Roger Lopes Alves; Vitor Pereira Vaz; Rodrigo Costa Puerari; Philippe Juneau; David Dewez; William Gerson Matias (Environmental Science and Pollution Research, 2023)

Investigating the effects of mesotrione/atrazine-based herbicide on honey bee foragers - Renan dos Santos Araújo; Thaís Andrade Viana; Lorena Lisbetd Botina; Daniel Silva Sena Bastos; Beatriz Cristina da Silva Alves; Mariana Machado-Neves; Rodrigo Cupertino Bernardes; Gustavo Ferreira Martins (Science of The Total Environment, 2023)

Biogenic signatures in the Cryogenian Brusque Metamorphic Complex, Brazil: Geochronological and paleoclimatological implications - Malton Carvalho Fraga; Fabrício Alves Mendes; Rodrigo Aguilar Guimarães; Carlos Eduardo de Mesquita Barros (Journal of South American Earth Sciences, 2023)

A novel strategy to predict clonal composites by jointly modeling spatial variation and genetic competition - Filipe M. Ferreira; Saulo F.S. Chaves; Leonardo L. Bhering; Rodrigo S. Alves; Elizabete K. Takahashi; João E. Sousa; Marcos D.V. Resende; Fernando P. Leite; Salvador A. Gezan; José M.S. Viana; Samuel B. Fernandes; Kaio O.G. Dias (Forest Ecology and Management, 2023)

Fermentative parameters and chemical composition of mixed silages from corn-crotalaria intercropping - Carolina M. Costa Araujo; Edgar S. Jara Galeano; Marco A.P. Orrico Junior; Tatiane Fernandes; Joyce P. Alves; Marciana Retore; Mabio S.J. Silva; Ana C.A. Orrico; Rodrigo A. Garcia; Luis A.Z. Machado (Animal Feed Science and Technology, 2023)

Spillover of avian seed dispersers between secondary forests and degraded areas in a tropical island - Rodrigo Béllo Carvalho; Kaizer J.F. Alves; Marco A. Pizo (Acta Oecologica, 2023)

Asymmetric response of Amazon forest water and energy fluxes to wet and dry hydrological extremes reveals onset of a local drought‐induced tipping point - Natalia Restrepo‐Coupe; Bradley O’Donnell Christoffersen; Marcos Longo; Luciana F. Alves; Kleber Silva Campos; Alessandro C. da Araujo; Raimundo C. de Oliveira; Neill Prohaska; Rodrigo da Silva; Raphael Tapajos; Kenia T. Wiedemann; Steven C. Wofsy; et al. (Global Change Biology, 2023)
Understanding the effects of intensification of Amazon basin hydrological cycling—manifest as increasingly frequent floods and droughts—on water and energy cycles of tropical forests is essential to meeting the challenge of predicting ecosystem responses to climate change, including forest “tipping points”. Here, we investigated the impacts of hydrological extremes on forest function using 12+ years of observations (between 2001–2020) of water and energy fluxes from eddy covariance, along with associated ecological dynamics from biometry, at the Tapajós National Forest. Measurements encompass the strong 2015–2016 El Niño drought and La Niña 2008–2009 wet events. We found that the forest responded strongly to El Niño‐Southern Oscillation (ENSO): Drought reduced water availability for evapotranspiration ( ET ) leading to large increases in sensible heat fluxes ( H ). Partitioning ET by an approach that assumes transpiration ( T ) is proportional to photosynthesis, we found that water stress‐induced reductions in canopy conductance ( G s ) drove T declines partly compensated by higher evaporation ( E ). By contrast, the abnormally wet La Niña period gave higher T and lower E , with little change in seasonal ET . Both El Niño‐Southern Oscillation (ENSO) events resulted in changes in forest structure, manifested as lower wet‐season leaf area index. However, only during El Niño 2015–2016, we observed a breakdown in the strong meteorological control of transpiration fluxes (via energy availability and atmospheric demand) because of slowing vegetation functions (via shutdown of G s and significant leaf shedding). Drought‐reduced T and G s , higher H and E , amplified by feedbacks with higher temperatures and vapor pressure deficits, signaled that forest function had crossed a threshold, from which it recovered slowly, with delay, post‐drought. Identifying such tipping point onsets (beyond which future irreversible processes may occur) at local scale is crucial for predicting basin‐scale threshold‐crossing changes in forest energy and water cycling, leading to slow‐down in forest function, potentially resulting in Amazon forests shifting into alternate degraded states.

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Unlocking the antioxidant and antimicrobial potential of flavone and amide-rich fractions from Conchocarpus macrocarpus (Rutaceae) leaves - Elielson Rodrigo Silveira; Priscila Bezerra Torres; Katia Castanho Scortecci; Hugo Alexandre Oliveira Rocha; Ivana Barbosa Suffredini; Jefferson de Souza Silva; Déborah Yara Alves Cursino dos Santos (Brazilian Journal of Botany, 2023)

A predatory social wasp does not avoid nestmates contaminated with a fungal biopesticide - André Rodrigues de Souza; Amanda Prato; Wilson Franca; Sircio Santos; Luan Dias Lima; Denise Araujo Alves; Rodrigo Cupertino Bernardes; Eduardo Fernando Santos; Fábio Santos do Nascimento; Maria Augusta Pereira Lima (Environmental Science and Pollution Research, 2023)

Real-time energy flow mapping: A VSM-based proposal for energy efficiency - Leonardo Fontoura; Daniel Luiz de Mattos Nascimento; Julio Vieira Neto; Noelia Garcia-Buendia; Jose Arturo Garza-Reyes; Gilson Brito Alves Lima; Guilherme Luz Tortorella; Rodrigo Goyannes Gusmão Caiado; Marcelo Jasmim Meiriño (Journal of Cleaner Production, 2023)

Fructooligosaccharide (FOS) and Galactooligosaccharide (GOS) Improve Neuroinflammation and Cognition By Up-regulating IRS/PI3K/AKT Signaling Pathway in Diet-induced Obese Mice - Igor Henrique Rodrigues de Paiva; Rodrigo Soares da Silva; Ingrid Prata Mendonça; Eduardo Duarte-Silva; José Roberto Botelho de Souza; Christina Alves Peixoto (Journal of Neuroimmune Pharmacology, 2023)

Ocean warming and CO2-driven acidification can alter the toxicity of metal-contaminated sediments to the meiofauna community - Giam Luca Altafim; Aline Vecchio Alves; Tailisi Hoppe Trevizani; Rubens Cesar Lopes Figueira; Fabiane Gallucci; Rodrigo Brasil Choueri (Science of The Total Environment, 2023)

Subacute high-refined carbohydrate diet leads to abnormal reproductive control of the hypothalamic-pituitary axis in female rats - Jeanini Zimerman; Oscar M.S. Niño; Charles S. da Costa; Jordana F. Zanol; Milena Comério; Letícia N. da Gama de Souza; Leandro Miranda-Alves; Rosiane A. Miranda; Patrícia C. Lisboa; Tays A. Camilo; Rodrigo Rorato; Guilherme Andrade Alves; et al. (Reproductive Toxicology, 2023)

Hepatic arteriovenous malformation in a calf - Yanca G.S. Soares; Jefferson S. Ferreira; Édipo M. Campos; Rodrigo C. Alves; Ialys M. Leite; Laynaslan A. Soares; Mirele A.S. Ferreira; Antonio F.M. Dantas; Franklin Riet-Correa; Glauco J.N. Galiza (Journal of Comparative Pathology, 2023)

Does macauba cake alter nutrient digestibility and microorganism population in the rumen of sheep? - Luciana Castro Geraseev; Eduardo Robson Duarte; Edvaldo Alves Vieira; Niurca González Ibarra; Amália Saturnino Chaves; Sarah Silva Santos; Alcinei Mistico Azevedo; Rodrigo Augusto Cortêz Passetti (Tropical Animal Health and Production, 2023)

A new genus of Aoridae and a new species of Bemlos Shoemaker, 1925 (Amphipoda: Senticaudata) from Northeastern Brazil - Jessika Alves; Marcos Moura Nogueira; Elizabeth G. Neves; Rodrigo Johnsson (Marine Biodiversity, 2023)

Metarhizium anisopliae E6 secretome reveals molecular players in host specificity and toxicity linked to cattle tick infection - Laura Rascovetzki Saciloto-de-Oliveira; Leonardo Broetto; Camila Innocente Alves; Rafael Lopes da Rosa; Yohana Porto Calegari Alves; Rodrigo Campos da Silva; Markus Berger; Alexandre José Macedo; Pedro Ferrari Dalberto; Cristiano Valim Bizarro; Jorge Almeida Guimarães; John R. Yates; et al. (Fungal Biology, 2023)

Water availability influences both wood anatomy and laticifer density in rubber tree saplings - Ícaro Renã Alves Moureira Nery; Paula Cristina Benetton Vergilio; Lucas Bertacini Viégas; Magali Ribeiro da Silva; Rafael Tassinari Resende; Matheus Peres Chagas; Marcelo Rodrigo Pace; Carmen Regina Marcati (Flora, 2023)

Chemical and ecotoxicological indicators for evaluating the treatment of coal mining wastes - Zuleica Carmen Castilhos; Ricardo Gonçalves Cesar; Silvia Gonçalves Egler; Renata Alamino; Danielly de Paiva Magalhães; Bruna Alves Pinheiro; Mariana Vezzone; Aline Freire Serrano; Rodrigo Sardinha Lourenço; Claudio Luiz Schneider (Environmental Science and Pollution Research, 2023)

Stainless steel and titanium alloys coated with sulfated chitosan to improve hemocompatibility properties - Sandy Danielle Lucindo Gomes; Maria Rosiene Antunes Arcanjo; Francisca Raysse Mesquita Silva; Luzia Kalyne Almeida Moreira Leal; Ana Paula Rosifini Alves Claro; Ketul Popat; Rodrigo Silveira Vieira (In vitro models, 2023)

Hitting the Road: Haplotype Diversity of Fire Ants Nesting on Disturbed Atlantic Forest Habitats - Juliana Maria Conceição Alves; Victor Hideki Nagatani; Otavio Guilherme Morais Silva; Manuela Oliveira Ramalho; Eduardo Gonçalves Paterson Fox; Rodrigo Fernando de Souza; Debora Yumi Kayano; Alexandre Wagner Silva Hilsdorf; Ricardo Harakava; Maria Santina de Castro Morini (Neotropical Entomology, 2023)

Lightweight carbon foam obtained from post-use polyethylene terephthalate bottles, properties, and potential applications - Marina Leticia Alves Ferreira; Tatiane Gomes Santos; Jose Marcio Fonseca Calixto; Rodrigo Lassarote Lavall; Danielle Diniz Justino; Fernanda Gabrielle Gandra; Tarcizo da Cruz Costa de Souza; Luiz Orlando Ladeira (Environmental Science and Pollution Research, 2023)

“Impact of aging on maximal oxygen uptake adjusted for lower limb lean mass, total body mass, and absolute values in runners” - Aldo Seffrin; Lavínia Vivan; Vinícius Ribeiro dos Anjos Souza; Ronaldo Alves da Cunha; Claudio Andre Barbosa de Lira; Rodrigo Luiz Vancini; Katja Weiss; Beat Knechtle; Marilia Santos Andrade (GeroScience, 2023)
Performance in endurance sports decreases with aging, which has been primarily attributed to cardiovascular and musculoskeletal aging; however, there is still no clear information on the factors that are most affected by aging. The aim of this study was to compare two groups of runners (< 50 and > 50 years of age) according to their absolute, weight-adjusted maximal oxygen uptake (V̇O 2 max ), lower limb lean mass-adjusted V̇O 2 max , ventilatory threshold, and respiratory compensation point (RCP). A total of 78 male recreational long-distance runners were divided into Group 1 (38.12 ± 6.87 years) and Group 2 (57.55 ± 6.14 years). Participants were evaluated for body composition, V̇O 2 max , VT, and RCP. Group 1 showed higher absolute and body mass-adjusted V̇O 2 max (4.60 ± 0.57 l·min −1 and 61.95 ± 8.25 ml·kg −1 ·min −1 , respectively) than Group 2 (3.77 ± 0.56 l·min −1 and 51.50 ± 10.22 ml·kg −1 ·min −1 , respectively), indicating a significant difference ( p < 0.001, d = − 1.46 and p < 0.001, d = − 1.16). Correspondingly, Group 1 showed a significantly higher lower limb lean mass–adjusted V̇O 2 max (251.72 ± 29.60 ml·kgLM −1 ·min −1 ) than Group 2 (226.36 ± 43.94 ml·kgLM −1 ·min −1 ) ( p = 0.008, d = − 0.71). VT (%V̇O 2 max ) ( p = 0.19, d = 0.19) and RCP (%V̇O 2 max ) ( p = 0.24, d = 0.22) did not differ between the groups. These findings suggest that both variables that are limited by central or peripheral conditions are negatively affected by aging, but the magnitude of the effect is higher in variables limited by central conditions. These results contribute to our understanding of how aging affects master runners.

Grain-cropping suitability for evaluating the agricultural land use change in Brazil - José Lucas Safanelli; Rogério de Souza Nóia Júnior; Pedro Alves Quilici Coutinho; Marcela Almeida de Araujo; Arthur Nicolaus Fendrich; Rodnei Rizzo; Ana Letícia Sbitkowski Chamma; Paulo André Tavares; Alberto Giaroli de Oliveira Pereira Barretto; Rodrigo Fernando Maule; Klaus Reichardt; Gerd Sparovek; et al. (Applied Geography, 2023)

Testicular toxicity in mice exposed to terephthalic acid in utero and during lactation - Gustavo Nazareno Monteiro; Douglas Santos Monteiro; Rodrigo Juliano Oliveira; Andréa Luiza Cunha-Laura; Ernani Aloysio Amaral; Sarah Alves Auharek (Environmental Science and Pollution Research, 2023)

Integrity assessment of the mooring lines and risers of floating production systems based on numerical models generated by retroanalysis of measured data: PART II – Integrity Assessment - Fabrício Nogueira Corrêa; Alexandra Silva Franz; Rodrigo Alves Pons; Breno Pinheiro Jacob (Ocean Engineering, 2023)

Does water temperature influence in microcystin production? A case study of Billings Reservoir, São Paulo, Brazil - Rodrigo Felipe Bedim Godoy; Elias Trevisan; André Aguiar Battistelli; Enzo Luigi Crisigiovanni; Elynton Alves do Nascimento; Artur Lourival da Fonseca Machado (Journal of Contaminant Hydrology, 2023)

Modeling covariance structures and optimizing Jatropha curcas breeding - Jeniffer Santana Pinto Coelho Evangelista; Marco Antônio Peixoto; Igor Ferreira Coelho; Filipe Manoel Ferreira; Tiago de Souza Marçal; Rodrigo Silva Alves; Saulo Fabricio da Silva Chaves; Erina Vitório Rodrigues; Bruno Gâlveas Laviola; Marcos Deon Vilela de Resende; Kaio Olimpio das Graças Dias; Leonardo Lopes Bhering (Tree Genetics & Genomes, 2023)

Paraprobiotics strains accelerate wound repair by stimulating re-epithelialization of NIH-3T3 cells, decreasing inflammatory response and oxidative stress - Monique Michels; Emily Córneo; Luana Bezerra Gonçalves Rocha; Rodrigo Dias; Ana Paula Lorenzen Voytena; Marina Rossetto; Fernanda Ramlov; Felipe Dal-Pizzol; Gabriel Fernandes Alves Jesus (Archives of Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Coconut water-based extender for seminal preservation in small ruminants: A meta-analysis study - Rogério Amorim dos Reis; Rodrigo de Nazaré Santos Torres; Iara Magalhães Ribeiro; Ciro Alexandre Alves Torres; Bruna Waddington de Freitas (Small Ruminant Research, 2023)

Integrity assessment of the mooring lines and risers of floating production systems based on numerical models generated by retroanalysis of measured data: PART I – Retroanalysis procedure - Fabrício Nogueira Corrêa; Rodrigo Alves Pons; Carl Horst Albrecht; Breno Pinheiro Jacob (Ocean Engineering, 2023)

Activity of endophytic fungi in enantioselective biotransformation of chiral amines: New approach for solid-state fermentation - Larissa Zambe Pinheiro; Fellipe Francisco da Silva; Maria Sandra Ramos Queiroz; Erika Cristina Gonçalves Aguieiras; Eliane Pereira Cipolatti; Aline Souza da Silva; Jonathan Bassut; Lucy Seldin; Denise Oliveira Guimarães; Denise Maria Guimarães Freire; Rodrigo Octávio Mendonça Alves de Souza; Ivana Correa Ramos Leal (Biocatalysis and Agricultural Biotechnology, 2023)

Genome-Based Characterization of Multidrug-Resistant Escherichia coli Isolated from Clinical Bovine Mastitis - Taila dos Santos Alves; Vinícius Sanches Rosa; Domingos da Silva Leite; Simony Trevizan Guerra; Sâmea Fernandes Joaquim; Felipe Freitas Guimarães; José Carlos de Figueiredo Pantoja; Simoni Baldini Lucheis; Vera Lúcia Mores Rall; Rodrigo Tavanelli Hernandes; Helio Langoni; Márcio Garcia Ribeiro (Current Microbiology, 2023)

Seasonality does not influence cortisol or testosterone production, or seminal quality of stallions located at low latitudes - Mariane Leão Freitas; João Henrique Moreira Viana; Margot Alves Nunes Dode; Selma Regina Maggiotto; Ivo Pivato; Thiago Rodrigues Cardoso Braga; Alexandre In Piao Gomes Lim; Rodrigo Arruda de Oliveira (Animal Reproduction Science, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Polymeric film containing pomegranate peel extract as a promising tool for the treatment of candidiasis - Geanne Aparecida de Paula; Nubya Nascimento Costa; Thais Martins da Silva; Kamila Arêas Bastos; Mariana Drummond Costa Ignacchiti; Juliana Aparecida Severi; Rodrigo Lambert Oréfice; Lílian Gasparelli Carreira; Janaina Cecília Oliveira Villanova; Juliana Alves Resende (Natural Product Research, 2023)

Development of a Digital Twin for smart farming: Irrigation management system for water saving - Rafael Gomes Alves; Rodrigo Filev Maia; Fábio Lima (Journal of Cleaner Production, 2023)

What are the factors associated with pregnancy loss after timed-artificial insemination in Bos indicus cattle? - Carlos E.C. Consentini; Rodrigo L.O.R. Alves; Mateus A. Silva; Juan P.A. Galindez; Guilherme Madureira; Laísse G. Lima; José R.S. Gonçalves; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2023)

Environmental degradation of vegetation cover and water bodies in the semiarid region of the Brazilian Northeast via cloud geoprocessing techniques applied to orbital data - Jhon Lennon Bezerra da Silva; Geber Barbosa de Albuquerque Moura; Marcos Vinícius da Silva; José Francisco de Oliveira-Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Daiana Caroline Refati; Ricardo da Cunha Correia Lima; Ailton Alves de Carvalho; Maria Beatriz Ferreira; José Ivaldo Barbosa de Brito; Roni Valter de Souza Guedes; Pabrício Marcos Oliveira Lopes; et al. (Journal of South American Earth Sciences, 2023)

Application of linear mixed models for multiple harvest/site trial analyses in perennial plant breeding - Saulo F. S. Chaves; Jeniffer S. P. C. Evangelista; Rodrigo S. Alves; Filipe M. Ferreira; Luiz A. S. Dias; Rafael M. Alves; Kaio O. G. Dias; Leonardo L. Bhering (Tree Genetics & Genomes, 2022)

Leveraging multi-harvest data for increasing genetic gains per unit of time for fruit yield and resistance to witches’ broom in Theobroma grandiflorum - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Rafael M. Alves; Jeniffer S. P. C. Evangelista; Kaio O. G. Dias (Euphytica, 2022)

Pre-treatment and continuous administration of simvastatin during sepsis improve metabolic parameters and prevent CNS injuries in survivor rats - Carlos Henrique Rocha Catalão; Anderson de Oliveira Souza; Nilton Nascimento Santos-Junior; Luis Henrique Angenendt da Costa; Jonathas Rodrigo dos Santos; Luciane Carla Alberici; Maria José Alves Rocha (Molecular and Cellular Biochemistry, 2022)

Selection index based on random regression model in ‘Tahiti’ acid lime - Renan Garcia Malikouski; Rodrigo Silva Alves; Marco Antônio Peixoto; Filipe Manoel Ferreira; Emanuel Ferrari do Nascimento; Andréia Lopes de Morais; Moises Zucoloto; Kaio Olimpio das Graças Dias; Leonardo Lopes Bhering (Euphytica, 2022)

Bioeconomic analysis of total replacement of corn grain with by-product from biscuit manufacture for purebred and crossbred Morada Nova lambs in feedlot system in the Brazilian semi-arid region - Aline Vieira Landim; Robson Mateus Freitas Silveira; José Rodrigo Rodrigues de Oliveira; Valdson José da Silva; Genilson Cesar Alves; Luiza de Nazaré Carneiro da Silva; Hélio Henrique Araújo Costa; Tereza Cristina Lacerda Gomes (Tropical Animal Health and Production, 2022)

Influence of the wavelength and intensity of LED lights and cytokinins on the growth rate and the concentration of total cardenolides in Digitalis mariana Boiss. ssp. heywoodii (P. Silva and M. Silva) Hinz cultivated in vitro - Giselly Mota da Silva; Alliyu Mohamed; Alexandre Alves de Carvalho; José Eduardo Brasil Pereira Pinto; Fernão Castro Braga; Rodrigo Maia de Pádua; Wolfgang Kreis; Suzan Kelly Vilela Bertolucci (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Metformin improves depressive-like behavior in experimental Parkinson’s disease by inducing autophagy in the substantia nigra and hippocampus - Ingrid Prata Mendonça; Igor Henrique Rodrigues de Paiva; Eduardo Pereira Duarte-Silva; Michel Gomes de Melo; Rodrigo S. da Silva; Maria Isabelly Xavier do Nascimento; Christina Alves Peixoto (Inflammopharmacology, 2022)

Does the same refuge signify the same reproductive tactics? Comparing the mating systems of two symbiont alpheid shrimps (Crustacea: Decapoda) - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Marine Ecology, 2022)
Animal populations can present different mating tactics according to the number of mates males or females obtain. The limiting factors for copulation in symbiont crustaceans are the size, structural complexity, and density of refuge, in addition to predation risk outside their shelters. In this study, we aimed to investigate, comparatively, if the occupation of the same refuge leads to the same reproductive tactic in two symbiont species of alpheid shrimps. For this purpose, we described the population distribution of Alpheus estuariensis , a burrowing shrimp, and Salmoneus carvachoi , a tenant species, in an intertidal mudflat in Pernambuco, northeastern Brazil. Alpheus estuariensis experiences sexual dimorphism relative to body and cheliped size, where males present larger body sizes and allocate more resources to cheliped growth than females. However, both males and females presented positive allometric growth in chelipeds. In S. carvachoi , male‐phase individuals reach smaller body sizes than hermaphrodites. Male‐phase shrimps experience positive allometry in cheliped size, while hermaphrodites do not. Both species were found inhabiting burrows as sexual pairs more frequently than expected by chance. Paired females of A. estuariensis were found carrying embryos more frequently than solitary ones. We did not find a statistical difference between the frequency of single and paired ovigerous hermaphrodites in S. carvachoi . Our results indicate that A. estuariensis is social monogamous, while S. carvachoi is promiscuous. We argue that different biological and ecological aspects of these species could explain the distinct tactics adopted by them. Alpheus estuariensis digs its own refuge and is a much larger species, bearing a more robust cheliped than S. carvachoi . Thus, we argue that the burrowing species ( A. estuariensis ) should monopolize and defend their refuge, and S. carvachoi only takes advantage of this resource.

Identifying suitable areas for common bottlenose dolphin in anthropized waters - Guilherme Maricato; Rodrigo Tardin; Liliane Lodi; Leonardo L. Wedekin; Fábio G. Daura-Jorge; Israel Maciel; Tatiana F. Maria; Maria Alice S. Alves (Marine Biology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

The industrial versatility of Gluconobacter oxydans: current applications and future perspectives - Gabrielle Alves Ribeiro da Silva; Simone Santos de Sousa Oliveira; Sara Fernandes Lima; Rodrigo Pires do Nascimento; Andrea Regina de Souza Baptista; Sorele Batista Fiaux (World Journal of Microbiology and Biotechnology, 2022)

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

New record of the bat falcon (Falco rufigularis) in northeastern Brazil: Implications for its future distribution under climate change - Maria Eduarda Alves Ferreira; Rodrigo Ferraz Jardim Marques; Hélio Francisco Leite; Alexandre M. Fernandes (Biologia, 2022)

A Genetic Model of Epilepsy with a Partial Alzheimer’s Disease-Like Phenotype and Central Insulin Resistance - Suélen Santos Alves; Rui Milton Patrício da Silva Junior; Polianna Delfino-Pereira; Marilia Gabriella Alves Goulart Pereira; Israel Vasconcelos; Hanna Schwaemmle; Rodrigo Focosi Mazzei; Maiko Luiz Carlos; Enilza Maria Espreafico; Antônio Claudio Tedesco; Adriano Sebollela; Sebastião Sousa Almeida; et al. (Molecular Neurobiology, 2022)

Redescription of Wallinia brasiliensis (Digenea: Allocreadiidae) from Astyanax lacustris (Osteichthyes: Characidae) in Brazil - Rodrigo Bravin Narciso; Diego Henrique Mirandola Dias Vieira; Karina Gabriele Alves Dias; Vanessa Doro Abdallah; Reinaldo José da Silva (Biologia, 2022)

Contrasting leaf cuticular wax composition of Conchocarpus and Dryades species (Rutaceae) from the Atlantic Forest and “Restinga” - Elielson Rodrigo Silveira; Lucas Paradizo Roma; José Rubens Pirani; Déborah Yara Alves Cursino dos Santos (Brazilian Journal of Botany, 2022)

Productive characteristics of feedlot Santa Inês and Dorper lambs: intake, digestibility, feeding behavior, performance, carcass traits, and meat quality - Rodrigo Brito Saldanha; Luis Gabriel Alves Cirne; Lara Maria Santos Brant; Carlindo Santos Rodrigues; Douglas dos Santos Pina; Susiane de Carvalho Matos; Amanda Bastos Grimaldi; Silvia Cheles Bento; Manuela Silva Libânio Tosto; Stefanie Alvarenga Santos; Henry Daniel Ruiz Alba; Gleidson Giordano Pinto de Carvalho (Tropical Animal Health and Production, 2022)

Genetic variability analyses considering multi-environment trials in maize breeding - Igor Ferreira Coelho; Renan Garcia Malikouski; Jeniffer Santana Pinto Coelho Evangelista; Marco Antônio Peixoto; Rodrigo Silva Alves; Jefferson Fernando Naves Pinto; Edésio Fialho dos Reis; Leonardo Lopes Bhering (Euphytica, 2022)

Microscale Toxicity Identification Evaluation (TIE) for interstitial water of estuarine sediments affected by multiple sources of pollution - Aline Vecchio Alves; Mariana Aliceda Ferraz; Beatriz Barbosa Moreno; Caio Rodrigues Nobre; Renata Medeiros Antunes; Fabio Hermes Pusceddu; Isabella Cristina da Costa Leal Bordon; Deborah Inês Teixeira Favaro; Marycel Elena Barbosa Cotrim; Rodrigo Brasil Choueri (Environmental Science and Pollution Research, 2022)

DNA Metabarcoding from Microbial Communities Recovered from Stream and Its Potential for Bioremediation Processes - Júlia Ronzella Ottoni; Rosane dos Santos Grignet; Maria Gabriela Azevedo Barros; Suzan Prado Fernandes Bernal; Andressa Alves Silva Panatta; Gileno Vieira Lacerda-Júnior; Victor Borin Centurion; Tiago Palladino Delforno; Caroline da Costa Silva Goncalves; Michel Rodrigo Zambrano Passarini (Current Microbiology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Avoiding burning practice and its consequences on the greenhouse gas emission in sugarcane areas southern Brazil - Luciano Ito Perillo; Ricardo de Oliveira Bordonal; Eduardo Barretto de Figueiredo; Mara Regina Moitinho; Daniel Alves Aguiar; Bernardo Friedrich Theodor Rudorff; Alan Rodrigo Panosso; Newton La Scala (Environmental Science and Pollution Research, 2022)

Theobroma grandiflorum breeding optimization based on repeatability, stability and adaptability information - Saulo Fabrício da Silva Chaves; Rafael Moysés Alves; Rodrigo Silva Alves; Alexandre Magno Sebbenn; Marcos Deon Vilela de Resende; Luiz Antônio dos Santos Dias (Euphytica, 2021)

IgG Subclass Analysis in Patients with Chagas Disease 4 Years After Benznidazole Treatment - Maurício Llaguno; Marcos Vinícius da Silva; Fernanda Rodrigues Helmo; Lara Rocha Batista; Djalma Alexandre Alves da Silva; Rodrigo Cunha de Sousa; Luiz Antonio Pertili Rodrigues de Resende; Eliane Lages-Silva; Carlo José Freire Oliveira; Juliana Reis Machado; Denise Bertulucci Rocha Rodrigues; Dalmo Correia; et al. (Acta Parasitologica, 2021)

Biomonitoring of surface water quality in the Chopim River within the Conservation Unit Campos de Palmas Wildlife Refuge, southern Brazil - Daiana Lauxen Schutz; Inara Giacobbo de Marco; Geiciane Locatelli Alves; José Vitor Abilhõa Vincoski; Sabrina Ishikawa; Ana Paula de Oliveira Schmitz; Eduardo Michel Vieira Gomes; Fernando Cesar Manosso; Ivane Benedetti Tonial; Juan Carlos Pokrywiecki; Rodrigo Lingnau; Ticiane Sauer Pokrywieki; et al. (Environmental Monitoring and Assessment, 2021)

Effects of biofloc effluent in different regimes as a fertilizer for Kappaphycus alvarezii: indoor maintenance and sea cultivation - Rodrigo De Martino; Luiza Vieira Mariot; Fernando Zwierzikowski da Silva; Carmen Simioni; Marcella Araújo do Amaral Carneiro; Eva Regina Oliveira; Marcelo Maraschin; Alex Alves dos Santos; Leila Hayashi (Journal of Applied Phycology, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Exploring the bioactivity potential of Leonotis nepetifolia : phytochemical composition, antimicrobial and antileishmanial activities of extracts from different anatomical parts - Diego Pinto de Oliveira; Letícia de Almeida; Marcos José Marques; Roberta Ribeiro de Carvalho; Amanda Latércia Tranches Dias; Geraldo Alves da Silva; Rodrigo Maia de Pádua; Fernão Castro Braga; Marcelo Aparecido da Silva (Natural Product Research, 2021)

Readily dispersible clay in soils from different Brazilian regions by visible, near, and mid-infrared spectral data - Isabela Mello Silva; Danilo Jefferson Romero; Clécia Cristina Barbosa Guimarães; Marcelo Rodrigo Alves; Lucas Prado Osco; Arnaldo Barros e Souza; Alvaro Pires da Silva; José A.M. Demattê (International Journal of Remote Sensing, 2021)

Temperature and productivity distinctly affect the species richness of ectothermic and endothermic multitrophic guilds along a tropical elevational gradient - Chaim J. Lasmar; Clarissa Rosa; Antônio C. M. Queiroz; Cássio A. Nunes; Mayara M. G. Imata; Guilherme P. Alves; Gabriela B. Nascimento; Ludson N. Ázara; Letícia Vieira; Júlio Louzada; Rodrigo M. Feitosa; Antonio D. Brescovit; et al. (Oecologia, 2021)

Positive selection of the long-wavelength opsin gene in South American cichlid fishes - Thomaz Mansini Carrenho Fabrin; Luciano Seraphim Gasques; Rodrigo Junio da Graça; Sônia Maria Alves Pinto Prioli; Weferson Júnio da Graça; Alberto José Prioli (Hydrobiologia, 2021)

Microbiome and oral squamous cell carcinoma: a possible interplay on iron metabolism and its impact on tumor microenvironment - Rodrigo Alex Arthur; Rafael dos Santos Bezerra; João Paulo Bianchi Ximenez; Bruna Laís Merlin; Raphael de Andrade Morraye; João Valentini Neto; Natália Melo Nasser Fava; David Livingstone Alves Figueiredo; Carlos Alberto Oliveira de Biagi; Maria Jara Montibeller; Jhefferson Barbosa Guimarães; Ellen Gomes Alves; et al. (Brazilian Journal of Microbiology, 2021)

The effects of anthropogenic noise on cetaceans in Brazil: the need to consider recent scientific advances in environmental licensing - Ana Luiza Mello Soares Pires; Israel de Sá Maciel; Maria Alice dos Santos Alves; Rodrigo Hipólito Tardin (Journal of Coastal Conservation, 2021)

A TIE Approach to Identify Substances Causing Sediment Pore Water Toxicity After a Major Fire at Fuel Storage Tanks in the Port of Santos (SE, Brazil) - Mariana Aliceda Ferraz; Aline Vecchio Alves; Rodrigo Brasil Choueri (Bulletin of Environmental Contamination and Toxicology, 2021)

Correction to: Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Production of Secreted Carbohydrates that Present Immunologic Similarities with the Cryptococcus Glucuronoxylomannan by Members of the Trichosporonaceae Family: A Comparative Study Among Species of Clinical Interest - Iara Bastos de Andrade; Marcos de Abreu Almeida; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Alessandra Leal da Silva Chaves; Susana Frases; Rosely Maria Zancopé-Oliveira; Fábio Brito-Santos; Rodrigo Almeida-Paes (Mycopathologia, 2021)

Evolution of virulence-related phenotypes of Sporothrix brasiliensis isolates from patients with chronic sporotrichosis and acquired immunodeficiency syndrome - Ingrid Ludmila Rodrigues Cruz; Dayvison Francis Saraiva Freitas; Priscila Marques de Macedo; Maria Clara Gutierrez-Galhardo; Antonio Carlos Francesconi do Valle; Marcos de Abreu Almeida; Rowena Alves Coelho; Fábio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2021)

Folic Acid-Doxorubicin-Double-Functionalized-Lipid-Core Nanocapsules: Synthesis, Chemical Structure Elucidation, and Cytotoxicity Evaluation on Ovarian (OVCAR-3) and Bladder (T24) Cancer Cell Lines - Rodrigo Cé; Vladimir Lavayen; Gabriela Klein Couto; João Guilherme Barreto De Marchi; Barbara Zoche Pacheco; Letícia Antunes Natividade; Tiago Ost Fracari; Taiane Medeiro Ciocheta; Aline de Cristo Soares Alves; Denise Soledade Jornada; Silvia Stanisçuaski Guterres; Fabiana Seixas; et al. (Pharmaceutical Research, 2021)

Application of graphene nanosheet oxide for atrazine adsorption in aqueous solution: synthesis, material characterization, and comprehension of the adsorption mechanism - Rodrigo de Souza Antônio; Ana Carolina Sestito Guerra; Murilo Barbosa de Andrade; Letica Nishi; Aline Takaoka Alves Baptista; Rosângela Bergamasco; Angélica Marquetotti Salcedo Vieira (Environmental Science and Pollution Research, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

Identification of Clinical and Laboratory Variables Associated with Cardiotoxicity Events Due to Doxorubicin in Breast Cancer Patients: A 1-Year Follow-Up Study - Ricardo Simões; Luciana Maria Silva; Angélica Navarro de Oliveira; Michelle Teodoro Alves; Rodrigo Mendonça Cardoso Pestana; Isabella Dâmaris Passos de Souza; Heloísa Helena Marques Oliveira; Cintia Esteves Soares; Adriano de Paula Sabino; Karina Braga Gomes (Cardiovascular Toxicology, 2021)

Selection of cowpea cultivars for high temperature tolerance: physiological, biochemical and yield aspects - Juliane Rafaele Alves Barros; Miguel Julio Machado Guimarães; Rodrigo Moura e Silva; Maydara Thaylla Cavalcanti Rêgo; Natoniel Franklin de Melo; Agnaldo Rodrigues de Melo Chaves; Francislene Angelotti (Physiology and Molecular Biology of Plants, 2021)

Preadministration of yerba mate (Ilex paraguariensis) helps functional activity and morphology maintenance of MC3T3-E1 osteoblastic cells after in vitro exposition to hydrogen peroxide - Gabrielli Collasanto Ceverino; Paula Katherine Vargas Sanchez; Roger Rodrigo Fernandes; Guilherme Alvarenga Alves; José Bernardo de Santis; Milla Sprone Tavares; Selma Siéssere; Karina Fittipaldi Bombonato-Prado (Molecular Biology Reports, 2021)

Pyriproxyfen does not cause microcephaly or malformations in a preclinical mammalian model - Juliana Miron Vani; Laynna de Carvalho Schweich-Adami; Sarah Alves Auharek; Andréia Conceição Millan Brochado Antoniolli-Silva; Rodrigo Juliano Oliveira (Environmental Science and Pollution Research, 2021)

Rosmarinic acid prevents gastric ulcers via sulfhydryl groups reinforcement, antioxidant and immunomodulatory effects - Raphaela Francelino do Nascimento; Rodrigo de Oliveira Formiga; Flávia Danielle Frota Machado; Igor Rafael Praxedes de Sales; Gedson Moraes de Lima; Edvaldo Balbino Alves Júnior; Giciane Carvalho Vieira; Raquel Fragoso Pereira; Aurigena Antunes de Araújo; Raimundo Fernandes de Araújo Junior; José Maria Barbosa Filho; Leônia Maria Batista (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Impact of high atmospheric CO2 concentrations on the seasonality of water-related processes, gas exchange, and carbohydrate metabolism in coffee trees under field conditions - Rodrigo Fazani Esteves Sanches; Danilo da Cruz Centeno; Marcia Regina Braga; Emerson Alves da Silva (Climatic Change, 2020)

Multi-trait multi-environment diallel analyses for maize breeding - Igor Ferreira Coelho; Rodrigo Silva Alves; João Romero do Amaral Santos de Car Rocha; Marco Antônio Peixoto; Larissa Pereira Ribeiro Teodoro; Paulo Eduardo Teodoro; Jefferson Fernando Naves Pinto; Edésio Fialho dos Reis; Leonardo Lopes Bhering (Euphytica, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Chemical analysis of the semipurified extract of Paullinia cupana and evaluation of in vitro inhibitory effects against Helicobacter pylori - Bruna Aparecida Alves Aguiar; Fernanda Giacomini Bueno; Gean Panizzon; Denise Brentan da Silva; Brena Ramos Athaydes; Rita de Cassia Ribeiro Gonçalves; Rodrigo Rezende Kitagawa; Leila Larisa Medeiros Marques; Mariana Nascimento de Paula; Tânia Mara Antonelli-Ushirobira; Daniela Cristina de Medeiros; João Carlos Palazzo de Mello (Natural Product Research, 2020)

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity - Rodrigo S. C. Cabral; Cassia C. F. Alves; Hellen R. F. Batista; Wendel C. Sousa; Isabela S. Abrahão; Antônio E. M. Crotti; Mariana B. Santiago; Carlos H. G. Martins; Mayker L. D. Miranda (Natural Product Research, 2020)

Ion Pair Strategy in Solid Lipid Nanoparticles: a Targeted Approach to Improve Epidermal Targeting with Controlled Adapalene Release, Resulting Reduced Skin Irritation - Linna B. O. Rodrigues; Flávia A. Lima; Camila P. B. Alves; Elisângela Martins-Santos; Marta M. G. Aguiar; Cleida A. Oliveira; Rodrigo L. Oréfice; Lucas A. M. Ferreira; Gisele A. C. Goulart (Pharmaceutical Research, 2020)

Comparative Analysis of Putative Virulence-Associated Factors of Microsporum canis Isolates from Human and Animal Patients - Mariana Lucy Mesquita Ramos; Rowena Alves Coelho; Fabio Brito-Santos; Davson Guimarães; Mario Premazzi; Rosely Maria Zancopé-Oliveira; Sandro Antônio Pereira; Isabella Dib Ferreira Gremião; Rosane Orofino-Costa; Maria Helena Galdino Figueiredo-Carvalho; Rodrigo Almeida-Paes (Mycopathologia, 2020)

Effect of cyclic heat stress on thyroidal hormones, thyroid histology, and performance of two broiler strains - João Paulo Rodrigues Bueno; Luciana Ruggeri Menezes Gotardo; Aline Monteiro dos Santos; Fernanda Heloisa Litz; Otávio Cintra Lemos Olivieri; Rodrigo Lemos Olivieri Rodrigues Alves; Cíntia Amaral Moraes; Mara Regina Bueno de Mattos Nascimento (International Journal of Biometeorology, 2020)

Effects of Microplastics Associated with Triclosan on the Oyster Crassostrea brasiliana: An Integrated Biomarker Approach - Caio Rodrigues Nobre; Beatriz Barbosa Moreno; Aline Vecchio Alves; Jonas de Lima Rosa; Heloisa da Rosa Franco; Denis Moledo de Souza Abessa; Luciane Alves Maranho; Rodrigo Brasil Choueri; Paloma Kachel Gusso-Choueri; Camilo Dias Seabra Pereira (Archives of Environmental Contamination and Toxicology, 2020)

Chitosan-Coated Lipid-Core Nanocapsules Functionalized with Gold-III and Bevacizumab Induced In Vitro Cytotoxicity against C6 Cell Line and In Vivo Potent Antiangiogenic Activity - Aline de Cristo Soares Alves; Vladimir Lavayen; Fabrício Figueiró; Danieli Rosane Dallemole; Amanda de Fraga Dias; Rodrigo Cé; Ana Maria Oliveira Battastini; Silvia Stanisçuaski Guterres; Adriana Raffin Pohlmann (Pharmaceutical Research, 2020)

Elucidation of the mechanism of anti-herpes action of two novel semisynthetic cardenolide derivatives - Laurita Boff; Naira Fernanda Zanchett Schneider; Jennifer Munkert; Flaviano Melo Ottoni; Gabriela Silva Ramos; Wolfgang Kreis; Fernão Castro Braga; Ricardo José Alves; Rodrigo Maia de Pádua; Cláudia Maria Oliveira Simões (Archives of Virology, 2020)

Estimates of repeatability coefficients and optimum number of measures for genetic selection of Cynodon spp. - Filipe Manoel Ferreira; João Romero do Amaral Santos de Carvalho Rocha; Rodrigo Silva Alves; Arthur Mayrink Elizeu; Flávio Rodrigo Gandolfi Benites; Marcos Deon Vilela de Resende; Fausto de Souza Sobrinho; Leonardo Lopes Bhering (Euphytica, 2020)

Prospecting for resistance of interspecific hybrids of Vitis spp. to Plasmopara viticola - Bruno Dias Amaral; Alexandre Pio Viana; Eileen Azevedo Santos; Rodrigo Moreira Ribeiro; Flavia Alves da Silva; Moisés Ambrósio; Andrew Michael Walker (Euphytica, 2020)

Optimization of Eucalyptus breeding through random regression models allowing for reaction norms in response to environmental gradients - Rodrigo Silva Alves; Marcos Deon Vilela de Resende; Camila Ferreira Azevedo; Fabyano Fonseca e Silva; João Romero do Amaral Santos de Car Rocha; Andrei Caíque Pires Nunes; Antônio Policarpo Souza Carneiro; Gleison Augusto dos Santos (Tree Genetics & Genomes, 2020)

Selenium improves photosynthesis and induces ultrastructural changes but does not alleviate cadmium-stress damages in tomato plants - Leticia Rodrigues Alves; Davi Rodrigo Rossatto; Mônica Lanzoni Rossi; Adriana Pinheiro Martinelli; Priscila Lupino Gratão (Protoplasma, 2020)

Molecular identification and antifungal susceptibility testing of Pucciniomycotina red yeast clinical isolates from Rio de Janeiro, Brazil - Fabio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Jean Carlos Almeida de Oliveira; Raissa Vieira Monteiro; Alessandra Leal da Silva Chaves; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2020)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Increased DNA damage is not associated to polymorphisms in OGGI DNA repair gene, CYP2E1 detoxification gene, and biochemical and hematological findings in soybeans farmers from Central Brazil - Fernanda Ribeiro Godoy; Hugo Freire Nunes; Alessandro Arruda Alves; Wanessa Fernandes Carvalho; Fernanda Craveiro Franco; Rodrigo Roncato Pereira; Alex Silva da Cruz; Cláudio Carlos da Silva; Rogério Pereira Bastos; Daniela de Melo e Silva (Environmental Science and Pollution Research, 2019)

Habitat use models of spatially auto-correlated data: a case study of the common bottlenose dolphin, Tursiops truncatus truncatus , in southeastern Brazil - Rodrigo H. Tardin; Yongwan Chun; Sheila M. Simão; Maria Alice S. Alves (Marine Biology Research, 2019)

Genome sequencing of Burkholderia contaminans LTEB11 reveals a lipolytic arsenal of biotechnological interest - Robson Carlos Alnoch; Rodrigo Luis Alves Cardoso; Dieval Guizelini; Eduardo Balsanelli; Michelle Zibetti Tadra-Sfeir; Fábio de Oliveira Pedrosa; Guilherme Lanzi Sassaki; Leonardo Magalhães Cruz; David Alexander Mitchell; Emanuel Maltempi de Souza; Nadia Krieger; Marcelo Muller-Santos (Brazilian Journal of Microbiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Study of physiological and enzymatic properties and characterization of pathogenic activity of a fungus isolated from moss Sanionia uncinata (Hedw.) Loeske in Antarctica - Graciéle Cunha Alves de Menezes; Rodrigo Paidano Alves; Filipe de Carvalho Victoria; Jair Putzke; Antonio Batista Pereira; Margeli Pereira de Albuquerque (Polar Biology, 2019)

Climate model for seasonal variation in Bemisia tabaci using CLIMEX in tomato crops - Rodrigo Soares Ramos; Lalit Kumar; Farzin Shabani; Ricardo Siqueira da Silva; Tamíris Alves de Araújo; Marcelo Coutinho Picanço (International Journal of Biometeorology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Identification and characterization of microsatellite loci in West Atlantic sea cucumber Holothuria grisea (Selenka 1867) - Vanessa Alves Pereira; Jamille Martins Forte; José Pedro Vieira Arruda-Júnior; Fábio Mendonça Diniz; Rodrigo Maggioni; Carminda Sandra Brito Salmito-Vanderley (Journal of Genetics, 2018)

Atlantic butterflies: a data set of fruit‐feeding butterfly communities from the Atlantic forests - Jessie Pereira dos Santos; André Victor Lucci Freitas; Keith Spalding Brown; Junia Yasmin Oliveira Carreira; Patrícia Eyng Gueratto; Augusto Henrique Batista Rosa; Giselle Martins Lourenço; Gustavo Mattos Accacio; Márcio Uehara‐Prado; Cristiano Agra Iserhard; Aline Richter; Karine Gawlinski; et al. (Ecology, 2018)
Butterflies are one of the best‐known insect groups, and they have been the subject of numerous studies in ecology and evolution, especially in the tropics. Much attention has been given to the fruit‐feeding butterfly guild in biodiversity conservation studies, due to the relative ease with which taxa may be identified and specimens sampled using bait traps. However, there remain many uncertainties about the macroecological and biogeographical patterns of butterflies in tropical ecosystems. In the present study, we gathered information about fruit‐feeding butterfly species in local communities from the Atlantic Forests of South America. The ATLANTIC BUTTERFLIES data set, which is part of ATLANTIC SERIES data papers, results from a compilation of 145 unpublished inventories and 64 other references, including articles, theses, and book chapters published from 1949 to 2018. In total, the data set contains 7,062 records (presence) of 279 species of fruit‐feeding butterflies identified with taxonomic certainty, from 122 study locations. The Satyrini is the tribe with highest number of species (45%) and records (30%), followed by Brassolini, with 13% of species and 12.5% of records. The 10 most common species correspond to 14.2% of all records. This data set represents a major effort to compile inventories of fruit‐feeding butterfly communities, filling a knowledge gap about the diversity and distribution of these butterflies in the Atlantic Forest. We hope that the present data set can provide guidelines for future studies and planning of new inventories of fruit‐feeding butterflies in this biome. The information presented here also has potential use in studies across a great variety of spatial scales, from local and landscape levels to macroecological research and biogeographical research. We expect that such studies be very important for the better implementation of conservation initiatives, and for understanding the multiple ecological processes that involve fruit‐feeding butterflies as biological indicators. No copyright restrictions apply to the use of this data set. Please cite this Data paper when using the current data in publications or teaching events.

Isolation of a larvicidal compound from Piper solmsianum C.DC. (Piperaceae) - Arthur Ladeira Macedo; Rodrigo Coutinho Duprat; Davyson de Lima Moreira; Maria Auxiliadora Coelho Kaplan; Thatyana Rocha Alves Vasconcelos; Laine Celestino Pinto; Raquel Carvalho Montenegro; Norman Arthur Ratcliffe; Cicero Brasileiro Mello; Alessandra Leda Valverde (Natural Product Research, 2018)

Multiple-trait BLUP: a suitable strategy for genetic selection of Eucalyptus - Rodrigo Silva Alves; João Romero do Amaral Santos de Carvalho Rocha; Paulo Eduardo Teodoro; Marcos Deon Vilela de Resende; Eduardo Pinheiro Henriques; Lidiane Aparecida Silva; Pedro Crescêncio Souza Carneiro; Leonardo Lopes Bhering (Tree Genetics & Genomes, 2018)

Resilience thinking applied to fisheries management: perspectives for the mullet fishery in Southern-Southeastern Brazil - Michelle Alves de Abreu-Mota; Rodrigo Pereira Medeiros; Mauricio Almeida Noernberg (Regional Environmental Change, 2018)

Weather-based coffee leaf rust apparent infection rate modeling - Fernando Dill Hinnah; Paulo Cesar Sentelhas; Carlos Alberto Alves Meira; Rodrigo Naves Paiva (International Journal of Biometeorology, 2018)

Identification of Mycobacterium species and Rhodococcus equi in peccary lymph nodes - Amanda Bonalume Cordeiro de Morais; Carmen Alicia Daza Bolaños; Ana Carolina Alves; Cássia Yumi Ikuta; Gustavo Henrique Batista Lara; Marcos Bryan Heinemann; Rogério Giuffrida; Fernando Paganini Listoni; Mateus de Souza Ribeiro Mioni; Rodrigo Garcia Motta; Shinji Takai; Márcio Garcia Ribeiro (Tropical Animal Health and Production, 2018)

Generation mean analysis for nitrogen and phosphorus uptake, utilization, and translocation indexes at vegetative stage in tropical popcorn - Vinícius Costa Almeida; José Marcelo Soriano Viana; Leonardo Alves Risso; Cleberson Ribeiro; Rodrigo Oliveira DeLima (Euphytica, 2018)

Higher phylogenetic diversity prevents loss of functional diversity caused by successive drying and rewetting cycles - Laura Bononi; Rodrigo Gouvêa Taketani; Danilo Tosta Souza; Marta Alves Moitinho; Vanessa Nessner Kavamura; Itamar Soares Melo (Antonie van Leeuwenhoek, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Heme oxygenase-1/biliverdin/carbon monoxide pathway downregulates hypernociception in rats by a mechanism dependent on cGMP/ATP-sensitive K+ channels - Hellíada Vasconcelos Chaves; Danielle Rocha do Val; Kátia Alves Ribeiro; Jonas Cavalcante Lemos; Ricardo Basto Souza; Francisco Isaac Fernandes Gomes; Rodrigo Maranguape Silva da Cunha; Vicente de Paulo Teixeira Pinto; Gerardo Cristino Filho; Marcellus Henrique Loiola Ponte de Souza; Mirna Marques Bezerra; Gerly Anne de Castro Brito (Inflammation Research, 2018)

Anti-inflammatory and antialgic actions of a nanoemulsion of Rosmarinus officinalis L. essential oil and a molecular docking study of its major chemical constituents - Raphaelle Sousa Borges; Emerson Silva Lima; Hady Keita; Irlon Maciel Ferreira; Caio Pinho Fernandes; Rodrigo Alves Soares Cruz; Jonatas Lobato Duarte; Josué Velázquez-Moyado; Brenda Lorena Sánchez Ortiz; Andrés Navarrete Castro; Jaderson Vieira Ferreira; Lorane Izabel da Silva Hage-Melim; et al. (Inflammopharmacology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

IL-33 signalling in liver immune cells enhances drug-induced liver injury and inflammation - Maísa Mota Antunes; Alan Moreira Araújo; Ariane Barros Diniz; Rafaela Vaz Sousa Pereira; Débora Moreira Alvarenga; Bruna Araújo David; Renata Monti Rocha; Maria Alice Freitas Lopes; Sarah Cozzer Marchesi; Brenda Naemi Nakagaki; Érika Carvalho; Pedro Elias Marques; et al. (Inflammation Research, 2018)

Tinea Capitis by Microsporum audouinii: Case Reports and Review of Published Global Literature 2000–2016 - Fábio Brito-Santos; Maria Helena Galdino Figueiredo-Carvalho; Rowena Alves Coelho; Anna Sales; Rodrigo Almeida-Paes (Mycopathologia, 2017)

Physical and chemical characteristics of the longissimus dorsi from swine reared in climate-controlled and uncontrolled environments - Juliana Lolli Malagoli de Mello; Mariana Piatto Berton; Rita de Cassia Dourado; Aline Giampietro-Ganeco; Rodrigo Alves de Souza; Fábio Borba Ferrari; Pedro Alves de Souza; Hirasilva Borba (International Journal of Biometeorology, 2017)

Arterial pulse wave propagation velocity in healthy dogs by pulse wave Doppler ultrasound - Rodrigo B. Nogueira; Lucas A. Pereira; Alice F. Basso; Ingrid S. da Fonseca; Lorena A. Alves (Veterinary Research Communications, 2017)

Inbred mice strain shows neurobehavioral changes when exposed to tannery effluent - Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Bruna de Oliveira Mendes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Mateus Flores Montalvão; Dieferson da Costa Estrela; Anderson Rodrigo da Silva; Guilherme Malafaia (Environmental Science and Pollution Research, 2017)

Differential tolerance to water deficit in two açaí (Euterpe oleracea Mart.) plant materials - Walter Vellasco Duarte Silvestre; Priscilla Andrade Silva; Lenilson Ferreira Palheta; Cândido Ferreira de Oliveira Neto; Rodrigo Otávio Rodrigues de Melo Souza; Reginaldo Alves Festucci-Buselli; Hugo Alves Pinheiro (Acta Physiologiae Plantarum, 2017)

Anxiety and memory deficits induced by tannery effluent in C57BL/6J female mice - Abraão Tiago Batista Guimarães; Raissa de Oliveira Ferreira; Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Anderson Rodrigo da Silva; Aline Sueli de LimaRodrigues; Daniela de Melo e Silva; Renata Mazaro e Costa; André Luis da Silva Castro; Guilherme Malafaia (Environmental Science and Pollution Research, 2016)

Liming in the sugarcane burnt system and the green harvest practice affect soil bacterial community in northeastern São Paulo, Brazil - Silvana Pompeia Val-Moraes; Helena Suleiman de Macedo; Luciano Takeshi Kishi; Rodrigo Matheus Pereira; Acacio Aparecido Navarrete; Lucas William Mendes; Eduardo Barretto de Figueiredo; Newton La Scala; Siu Mui Tsai; Eliana Gertrudes de Macedo Lemos; Lúcia Maria Carareto Alves (Antonie van Leeuwenhoek, 2016)

Mesophotic reef fish assemblages of the remote St. Peter and St. Paul’s Archipelago, Mid-Atlantic Ridge, Brazil - Marcos Rogerio Rosa; Aline Cristina Alves; Diego Valverde Medeiros; Ericka Oliveira Cavalcanti Coni; Camilo Moitinho Ferreira; Beatrice Padovani Ferreira; Ricardo de Souza Rosa; Gilberto Menezes Amado-Filho; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Fabiano Lopes Thompson; Paulo Yukio Gomes Sumida; et al. (Coral Reefs, 2016)

Microbial community diversity and physical–chemical features of the Southwestern Atlantic Ocean - Nelson Alves Junior; Pedro Milet Meirelles; Eidy de Oliveira Santos; Bas Dutilh; Genivaldo G. Z. Silva; Rodolfo Paranhos; Anderson S. Cabral; Carlos Rezende; Tetsuya Iida; Rodrigo L. de Moura; Ricardo Henrique Kruger; Renato C. Pereira; et al. (Archives of Microbiology, 2015)

A physiological study of integument secretions in the marine polychaete Eulalia viridis and their potential biotechnological value. - Rodrigo Ana; Alves De Matos António; Carrapiço Francisco; Costa Maria; Costa Pedro (Frontiers in Marine Science, 2014)

Regeneration and characterization of somatic hybrids combining sweet orange and mandarin/mandarin hybrid cultivars for citrus scion improvement - Leonardo Soriano; Francisco de Assis Alves Mourão Filho; Luis Eduardo Aranha Camargo; Mariangela Cristofani-Yaly; Rodrigo Rocha Latado; Camila de Andrade Pacheco; Fernando Alves de Azevedo; Beatriz Madalena Januzzi Mendes (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Synchronous Oral Paracoccidioidomycosis and Esophageal Carcinoma - Paulo Victor Alves Tubino; Bruno Jose de Queiroz Sarmento; Vitorino Modesto dos Santos; Estevão Ribeiro Borges; Lucas Evangelista Correia da Silva; Rodrigo de Souza Lima (Mycopathologia, 2012)

In vitro comparative analysis of cryopreservation of undifferentiated mesenchymal cells derived from human periodontal ligament - Rodrigo Gadelha Vasconcelos; Rodrigo Alves Ribeiro; Marcelo Gadelha Vasconcelos; Kenio Costa Lima; Carlos Augusto Galvão Barboza (Cell and Tissue Banking, 2012)

Transcriptional Profiles of Roots of Different Soybean Genotypes Subjected to Drought Stress - Renata Stolf-Moreira; Eliana G. M. Lemos; Lúcia Carareto-Alves; Jackson Marcondes; Selma S. Pereira; Amanda A. P. Rolla; Rodrigo M. Pereira; Norman Neumaier; Eliseu Binneck; Ricardo V. Abdelnoor; Maria C. N. de Oliveira; Francismar C. Marcelino; et al. (Plant Molecular Biology Reporter, 2011)

Effects of metformin on glucose metabolism of perfused rat livers - Francielli Maria de Souza Silva; Mário Henrique Rocha Alves da Silva; Adelar Bracht; Gabrielle Jacklin Eller; Rodrigo Polimeni Constantin; Nair Seiko Yamamoto (Molecular and Cellular Biochemistry, 2010)

Heart failure increases atrogin-1 and MuRF1 gene expression in skeletal muscle with fiber type-specific atrophy - Robson Francisco Carvalho; Eduardo Paulino Castan; Cesar Augusto Coelho; Francis Silva Lopes; Fernanda Losi Alves Almeida; Aline Michelin; Rodrigo Wagner Alves de Souza; João Pessoa Araújo; Antonio Carlos Cicogna; Maeli Dal Pai-Silva (Journal of Molecular Histology, 2010)

Challenges and Prospects of Fisheries Co-Management under a Marine Extractive Reserve Framework in Northeastern Brazil - Rodrigo Leão De Moura; Carolina Viviana Minte-Vera; Isabela Baleeiro Curado; Ronaldo Bastos Francini-Filho; Hélio De Castro Lima Rodrigues; Guilherme Fraga Dutra; Diego Corrêa Alves; Francisco José Bezerra Souto (Coastal Management, 2009)

Cytotoxic, immunosuppressive and trypanocidal activities of agrocybin, a polyacetylene produced by Agrocybe perfecta (Basidiomycota) - Luiz H. Rosa; Elaine M. Souza-Fagundes; Kátia M.G. Machado; Tânia M. A. Alves; Olindo A. Martins-Filho; Alvaro J. Romanha; Rodrigo C. Oliveira; Carlos A. Rosa; Carlos L. Zani (World Journal of Microbiology and Biotechnology, 2006)

Asymptomatic Presentation of Chronic Pulmonary Paracoccidioidomycosis: Case Report and Review - José Wellington Alves dos Santos; Rodrigo Benedetti Debiasi; Jader Nascimento Miletho; Alessandra Naimaier Bertolazi; Ariovaldo Leal Bertolazi; Gustavo Trindade Michel (Mycopathologia, 2004)

A novel strain of Streptomyces malaysiensis isolated from Brazilian soil produces high endo-β-1,4-xylanase titres - Rodrigo Pires do Nascimento; Susana Marques; Luís Alves; Francisco Gírio; Maria Teresa Amaral-Collaço; Doralice Rodrigues Sacramento; Elba Pinto da Silva Bon; Rosalie Reed Rodrigues Coelho (World Journal of Microbiology and Biotechnology, 2003)